Toner

By using block polymerization of non-crystalline and crystalline resins in the toner, the ratio of tetrahydrofuran-insoluble substances and heat absorption of the resin components is controlled, and it is difficult to take into account both low-temperature fixing and heat-resistant fouling in the prior art in the prior art. The problem of efficient concentration uniformity and image quality are achieved.

CN112415871BActive Publication Date: 2024-12-17CANON KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202010849964.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-21
Filing Date
2020-08-21
Publication Date
2024-12-17
Estimated Expiration
2040-08-21

AI Technical Summary

Technical Problem

The prior art is difficult to achieve low-temperature fixing and heat-fouling resistance of toner at low temperatures, and at the same time there is a problem of uneven concentration, especially when concave and convex surfaces such as copper plate paper are used.

Method used

Using resin containing amorphous and crystalline parts as the binder resin, ensure adjustment by controlling the proportion of tetrahydrofuran insoluble substances in the resin component and the maximum endothermic peak temperature and heat absorption measured by a differential scanning calorimeter. The low-temperature fixing property and heat-fouling resistance of the toner are improved through block polymerization.

Benefits of technology

It realizes the clarity and heat-fouling resistance of the fixing image at low temperatures, while avoiding the problem of uneven concentrations and improving the overall performance of the toner.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112415871B_ABST
    Figure CN112415871B_ABST
Patent Text Reader

Abstract

The present invention relates to a toner. A toner comprising a resin containing a non-crystalline part and a crystalline part as a binder resin, wherein the ratio of tetrahydrofuran-insoluble matter of the resin component is 40% by mass to 80% by mass; in a differential scanning calorimeter measurement of the tetrahydrofuran-insoluble matter, when the temperature of the maximum endothermic peak is represented by Tm [°C] and the amount of endothermic heat is represented by H(I) [J / g], the following formulas (1) and (2) are satisfied: 55.0≤Tm≤80.0(1)10.0≤H(I)≤80.0(2).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a toner suitable for an image forming method using an electrophotographic method, an electrostatic recording method, or a toner jet recording method. Background Art

[0002] In recent years, even in the field of electrophotographic devices such as copiers and printers, energy conservation has been recognized as a major technical issue. To address this issue, it is necessary to significantly reduce the amount of heat applied to the fixing device. Consequently, there is a need for toners that can be fixed with low heat, that is, toners with satisfactory low-temperature fixing properties.

[0003] Conventionally, in order to enable fixing at relatively low temperatures, a method of making the binder resin into a sharper melt is known as one of the effective methods. In this regard, toners using crystalline resins have been introduced. Since crystalline resins do not exhibit a clear glass transition due to the arrangement of their molecular chains and have the property of not easily softening to the crystalline melting point, crystalline resins are being studied as materials that can achieve both heat-resistant storage stability and low-temperature fixing properties.

[0004] Furthermore, the number of media types is increasing. There is a strong demand for coated paper with a heavy basis weight and a highly uneven surface. This requires the rapid melting properties of crystalline resins to ensure penetration into the paper fibers of the coated paper. However, while the use of crystalline resins improves rapid melting properties, they lack elasticity at high temperatures and are prone to heat deterioration. Therefore, it is conceivable to ensure elasticity at high temperatures by mixing crystalline resins with amorphous resins, but in this case, sufficient rapid melting properties are not achieved.

[0005] In addition, by controlling the cross-linking structure of the binder resin within the colorant particles, the elasticity of the colorant at high temperatures can be controlled, but in the concave portions of the coated paper, heat is less likely to be applied during the fixing process, so the plasticity of the cross-linked resin is reduced, concentration unevenness occurs, and low-temperature fixing ability is reduced.

[0006] Japanese Patent Application Laid-Open No. 2007-114635 suggests that using a block copolymer obtained by esterifying a crystalline polyester block and a non-crystalline block for a pulverized toner enables fixing by low-temperature heating.

[0007] Furthermore, Japanese Patent Application Laid-Open No. 2010-145929 proposes a method for producing an electrophotographic toner, comprising melt-kneading a crystalline polyester obtained by polycondensation of an alcohol component and a carboxylic acid component containing an unsaturated aliphatic dicarboxylic acid compound and a non-crystalline resin in the presence of a radical polymerization initiator.

[0008] In this document, recrystallization of the crystalline polyester is promoted in the cooling step after kneading by partially crosslinking the crystalline polyester with carbon-carbon bonds to increase the molecular weight.

[0009] Japanese Patent Application Publication No. 2018-156074 proposes a toner containing a crystalline resin and a non-crystalline resin containing a long-chain alkyl group. This document specifies the ratio of the amount of heat absorbed by the toner binder in a second temperature-raising process after cooling from the first temperature-raising process based on an endothermic peak derived from the crystalline resin (A) to the amount of heat absorbed by the toner binder in the first temperature-raising process based on an endothermic peak derived from the crystalline resin (A), the endothermic peak being measured using a differential scanning calorimeter (DSC). Summary of the Invention

[0010] However, based on the results of research conducted on Japanese Patent Application Laid-Open No. 2007-114635, the present inventors found that when a block copolymer is used and heated above the melting point, the crystallinity of the crystalline resin is destroyed, sharp melting properties are reduced, and low-temperature fixing properties are impaired.

[0011] Furthermore, based on the results of studies conducted on Japanese Patent Application Publication No. 2010-145929, the inventors of the present invention found that when attempts are made to maintain a state in which recrystallization is promoted, elasticity on the high temperature side becomes insufficient, hot offset is likely to occur, and concentration unevenness is likely to occur.

[0012] In addition, based on the results of a study on a colorant produced using the colorant binder disclosed in Japanese Patent Application Publication No. 2018-156074, the inventors of the present invention found that although the crystalline resin is excellent in rapid melting properties, plasticization of the non-crystalline resin containing a cross-linked structure is less likely to proceed, and therefore, low-temperature fixing properties are not improved.

[0013] With these configurations, satisfactory results were not obtained for any of the low-temperature fixability determined by rapid melting properties, the fixability at high temperatures (hot offset resistance), and the elimination of density unevenness. As described above, further improvements are needed for toners in which crystalline sites are introduced into the binder resin.

[0014] An object of the present invention is to provide a toner that ensures low-temperature fixability, hot offset resistance, and elimination of density unevenness.

[0015] A toner comprising

[0016] A resin containing an amorphous portion and a crystalline portion as a binder resin, wherein

[0017] The ratio of tetrahydrofuran-insoluble matter of the resin component is 40% by mass to 80% by mass,

[0018] The ratio is calculated by the following formula:

[0019] Ratio of tetrahydrofuran-insoluble matter of resin component=(mass of tetrahydrofuran-insoluble matter of resin component in the toner) / (mass of resin component in the toner)×100,

[0020] In the differential scanning calorimeter measurement of the tetrahydrofuran-insoluble matter,

[0021] In the case where the temperature of the maximum endothermic peak is represented by Tm [° C.] and the amount of endothermic heat is represented by H(I) [J / g],

[0022] Satisfy the following equations (1) and (2):

[0023] 55.0≤Tm≤80.0 (1)

[0024] 10.0≤H(I)≤80.0 (2)

[0025] According to the present invention, a toner that ensures low-temperature fixability, hot offset resistance, and elimination of density unevenness can be provided.

[0026] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a schematic diagram of a measurement sample and a fixture for measuring viscoelasticity; and

[0028] Figure 2 Schematic diagram of the device used to measure triboelectric charge. DETAILED DESCRIPTION

[0029] Unless otherwise stated, the description of a numerical range "from XX to YY" or "XX to YY" means that the numerical range includes the lower limit and the upper limit as endpoints.

[0030] In the present specification, when a numerical range is described in sections, the upper limit and the lower limit of each numerical range can be arbitrarily combined.

[0031] As used herein, a resin having crystallinity refers to a resin having a clear endothermic peak in differential scanning calorimetry measurement.

[0032] Next, the toner will be described.

[0033] The fixing step in the electrophotographic method is a step of fixing the toner to the transfer material by applying heat and pressure to the toner for an extremely short time.

[0034] The toner contains a resin containing an amorphous portion and a crystalline portion as a binder resin.

[0035] By introducing a crystalline site as described in Background Art, it becomes possible to produce a toner having excellent sharp melting properties. The term "sharp melting properties" as used herein refers to a behavior in which melting begins when the temperature rises while heat is applied to the toner.

[0036] In order to impart hot offset resistance to the toner, it is conceivable to improve the elasticity of the amorphous portion. For example, the elasticity can be controlled by introducing a cross-linked structure into the amorphous portion.

[0037] Therefore, there is a means for incorporating into the binder resin of the toner a crystalline site having sharp melting properties required to maintain low-temperature fixability and an amorphous site maintaining high-temperature elasticity required to impart hot offset resistance.

[0038] However, when using a binder resin obtained by simply mixing a crystalline resin having a crystalline portion with the aforementioned characteristics and an amorphous resin having an amorphous portion, the molten crystalline resin detaches from the toner particles during the toner melting step, causing hot offset. Furthermore, when using a transfer material with numerous uneven surfaces, such as coated paper, during fixing, the distance between the fixing member and the toner becomes uneven, and the contact time varies, resulting in uneven heating. As a result, uneven melting of the toner is likely to occur, leading to uneven density (mottling) in the image.

[0039] Furthermore, when the amorphous portion has a cross-linked structure, the mobility of the molecular structure decreases and the glass transition temperature increases, so plasticization is less likely to proceed during fixing. Therefore, when fixing at low temperatures, when using a transfer material such as coated paper, the adhesion between toner particles weakens, part of the fixed image is lost, and the fixed toner adheres to the roller during the fixing process, etc., and white spots (missing portions) appear on the image.

[0040] Therefore, as a result of intensive studies, the present inventors have found that any adverse effects can be eliminated by using a binder resin in which block polymerization of a crystalline site and a non-crystalline site has proceeded.

[0041] In the block-polymerized binder resin, the crystalline and amorphous sites have a microphase-separated structure. Therefore, even when the crystalline sites are rapidly plasticized during the fixing step, separation from the amorphous sites is prevented, improving hot offset resistance. Furthermore, since the crystalline sites are plasticized, the amorphous sites are also fully plasticized, rapidly promoting bonding between toner particles during low-temperature fixing, making the occurrence of white spots less likely. Furthermore, since the toner base particles are more likely to melt uniformly, density unevenness is eliminated.

[0042] In the differential scanning calorimeter measurement of the tetrahydrofuran (hereinafter, also referred to as THF)-insoluble matter of the resin component in the toner, when the temperature of the maximum endothermic peak is represented by Tm [° C.] and the amount of endothermic heat is represented by H(I) [J / g], the following formulas (1) and (2) need to be satisfied.

[0043] 55.0≤Tm≤80.0 (1)

[0044] 10.0≤H(I)≤80.0 (2)

[0045] If the Tm is less than 55.0°C, the toner's heat-resistant storage stability cannot be satisfied. Furthermore, if the Tm exceeds 80.0°C, the temperature applied to the transfer material during fixing must be very high, and low-temperature fixing properties deteriorate. The Tm is preferably 58.0°C to 77.0°C, and more preferably 60.0°C to 77.0°C. The Tm can be controlled by the composition of the crystalline resin.

[0046] If the endothermic heat value H(I) is less than 10.0 J / g, block polymerization of the crystalline and amorphous sites contained in the binder resin is insufficient, plasticization of the amorphous sites does not proceed, and white spots appear. Furthermore, if the endothermic heat value is low, the amorphous resin melts unevenly between toner particles, resulting in uneven concentration and reduced hot offset resistance. The endothermic heat value H(I) is preferably 11.5 J / g or greater, more preferably 13.0 J / g or greater, and even more preferably 16.5 J / g or greater.

[0047] Meanwhile, if H(I) exceeds 80.0 J / g, the amount of heat absorbed becomes excessively high, requiring a significant amount of heat to melt the entire toner. Consequently, when printing images on a large number of sheets at high speed, sufficient heat for melting the toner cannot be ensured, causing the toner on the image to peel off and potentially causing white spots to appear. The amount of heat absorbed H(I) is preferably 65.0 J / g or less, more preferably 50.0 J / g or less, and even more preferably 40.0 J / g or less.

[0048] H(I) can be controlled by the degree of bonding between the crystalline site and the non-crystalline site, and the degree of bonding can be controlled by the amount of the polymerization initiator added and the concentration of carbon-carbon bonds contained in the cross-linked polyester used as a raw material for the non-crystalline site.

[0049] The amount of THF-insoluble matter in the resin component in the toner needs to be 40% by mass to 80% by mass.

[0050] If the insoluble content ratio is less than 40% by mass, the high-temperature elasticity imparted by the crosslinked structure of the amorphous sites becomes insufficient, and hot offset resistance cannot be ensured. If the insoluble content ratio exceeds 80% by mass, the toner's elasticity is too high, resulting in reduced low-temperature fixability and an inability to ensure a sufficient fixed area. Furthermore, when printing a large number of sheets during the fixing step, toner melting becomes uneven, and image spots may appear.

[0051] The ratio of tetrahydrofuran-insoluble matter of the resin component is 40% by mass to 80% by mass,

[0052] The ratio is calculated by the following formula:

[0053] Ratio of tetrahydrofuran-insoluble matter of resin component=(mass of tetrahydrofuran-insoluble matter of resin component in toner) / (mass of resin component in toner)×100.

[0054] The amount of THF-insoluble matter is preferably 45% to 78% by mass, more preferably 50% to 77% by mass, and even more preferably 53% to 76% by mass. The proportion of THF-insoluble matter can be controlled by the composition and molecular weight of the crystalline and amorphous sites, and the degree of bonding between the crystalline and amorphous sites. The degree of bonding can also be controlled by the amount of the polymerization initiator added (described later) and the concentration of carbon-carbon bonds in the cross-linked polyester used as a raw material for the amorphous site.

[0055] In the toner, the non-crystalline site is preferably a non-crystalline modified resin site (cross-linked polyester resin) in which a crystalline vinyl resin and a polyester resin are cross-linked with each other via carbon-carbon bonds. The crystal structure of the vinyl resin before cross-linking is destroyed by the cross-linking of the vinyl resin and the polyester resin, so that the modified resin site becomes non-crystalline.

[0056] Hereinafter, a method for producing the binder resin will be described.

[0057] The binder resin preferably contains a non-crystalline cross-linked polyester resin portion as a non-crystalline portion in which a vinyl resin having crystallinity and a polyester resin are cross-linked with each other via a carbon-carbon bond, and a vinyl resin portion as a crystalline portion having crystallinity.

[0058] For example, when mixing a cross-linked polyester resin, a crystalline vinyl resin, and an additive, the mixing method may be a commonly known method. Examples of the mixing method include powder mixing, solvent mixing, and melt mixing. Examples of mixing devices used for powder mixing include Henschel mixers, Nauta mixers, and Banbury mixers. A Henschel mixer is preferred.

[0059] As the solvent mixing method, the following methods can be used: a method in which a cross-linked polyester resin and a crystalline vinyl resin are dissolved in an organic solvent and homogenized, followed by desolvation and pulverization; and a method in which a cross-linked polyester resin and a crystalline vinyl resin are dissolved in an organic solvent, dispersed in water, and then granulated and desolvated.

[0060] The melt mixing can be performed by crosslinking the polyester resin having carbon-carbon double bonds while melt mixing the polyester resin having carbon-carbon double bonds and the vinyl resin having crystallinity to form a crosslinked polyester resin, thereby obtaining the binder resin.

[0061] Examples of mixing devices used for melt mixing include batch mixing devices such as reaction tanks and continuous mixing devices. Continuous mixing devices are preferred for uniform mixing at an appropriate temperature in a short time. Examples of continuous mixing devices include twin-screw extruders, static mixers, extruders, continuous kneaders, and three-rollers.

[0062] In addition, the cross-linked polyester resin, the vinyl resin having crystallinity, and the additives may be mixed simultaneously when producing the toner. Among these methods, melt mixing that ensures uniform mixing and does not require solvent removal is preferred.

[0063] Among these methods, a method of crosslinking a crystalline vinyl resin and a polyester resin having carbon-carbon double bonds while melt-mixing is preferred. This method reacts the carbon-carbon double bonds of the polyester resin having carbon-carbon double bonds. This method can also be achieved by crosslinking by abstracting hydrogen atoms bonded to carbon atoms contained in the polyester resin having carbon-carbon double bonds through a hydrogen abstraction reaction induced by heating or the like.

[0064] In addition, in this production method, a hydrogen abstraction reaction can be simultaneously induced in the main chain of the crystalline vinyl resin by adding a free radical initiator or the like. This allows the polyester resin having a carbon-carbon double bond to react with the crystalline vinyl resin to achieve block polymerization of the binder resin (conversion into a cross-linked polyester resin).

[0065] As a specific method for performing such melt mixing, a mixture of a polyester resin having a carbon-carbon double bond and a vinyl resin having crystallinity is injected into, for example, a twin-screw extruder at a constant rate, and a radical reaction initiator is also injected at a constant rate, and the mixture is reacted while kneading and conveying, preferably at a temperature of 100° C. to 200° C.

[0066] In this case, the polyester resin having carbon-carbon double bonds and the crystalline vinyl resin as the reaction raw materials to be fed or injected into the twin-screw extruder can be directly injected into the extruder without cooling the reaction solution of each resin. The resin produced once can be cooled, pulverized, and then fed to the twin-screw extruder.

[0067] The method of melt mixing is not limited to these specific exemplified methods. For example, a suitable method may include adding the raw materials to a reaction vessel, heating to a temperature at which they are in a solution state, and mixing.

[0068] The binder resin for toner may include a compound used during polymerization of a vinyl resin having crystallinity and a residue thereof.

[0069] In producing the binder resin, from the viewpoint of improving low-temperature fixing property, hot offset resistance and heat-resistant storage stability, the mixing mass ratio of the vinyl resin having crystallinity and the polyester resin having a carbon-carbon double bond (vinyl resin / polyester resin) is preferably 45 / 55 to 95 / 5, more preferably 48 / 52 to 80 / 20, and further preferably 50 / 50 to 70 / 30.

[0070] The mass ratio of the crystalline site to the non-crystalline site in the binder resin (crystalline site / non-crystalline site) is preferably from 18 / 82 to 65 / 35, and more preferably from 22 / 78 to 55 / 45.

[0071] The number average molecular weight Mn of the binder resin is preferably about 5000 to 40,000, and more preferably about 8000 to 20,000.

[0072] The weight average molecular weight Mw of the binder resin is preferably about 10,000 to 80,000, more preferably about 20,000 to 60,000.

[0073] The ratio (Mw / Mn) of the weight average molecular weight Mw to the number average molecular weight Mn in the binder resin is preferably about 2.5 to 6.0, and more preferably about 3.0 to 5.0.

[0074] The radical reaction initiator is not particularly limited, and examples thereof include inorganic peroxides, organic peroxides, azo compounds, etc. In addition, these radical reaction initiators may be used in combination.

[0075] The inorganic peroxide is not particularly limited, and examples thereof include hydrogen peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, and the like.

[0076] The organic peroxide is not particularly limited, and examples thereof include benzoyl peroxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, α,α-bis(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, di-tert-hexyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxyhexanoate, acetyl peroxide, isobutyl peroxide, octanoyl peroxide, decanoyl peroxide, lauroyl peroxide, 3,3,5-trimethylhexanoyl peroxide, m-toluoyl peroxide, tert-butyl peroxyisobutyrate, tert-butyl peroxyneodecanoate, cumyl peroxyneodecanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropylmonocarbonate, and tert-butyl peroxyacetate.

[0077] The azo compound or diazo compound is not particularly limited, and examples thereof include 2,2′-azobis-(2,4-dimethylvaleronitrile), 2,2′-azobisisobutyronitrile, 1,1′-azobis(cyclohexane-1-carbonitrile), 2,2′-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile.

[0078] Among them, organic peroxides are preferred because they have high initiator efficiency and do not form toxic byproducts such as cyanide compounds. In addition, since the cross-linking reaction proceeds efficiently and the amount used can be small, it is more preferable to use a reaction initiator with high hydrogen abstraction ability, and free radical reaction initiators with high hydrogen abstraction ability such as tert-butyl peroxyisopropyl monocarbonate, benzoyl peroxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, α,α-bis(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane and di-tert-hexyl peroxide are particularly preferred.

[0079] The amount of the radical reaction initiator used is not particularly limited, but a preferred amount is 0.1 to 10.0 parts by mass relative to 100.0 parts by mass of the vinyl resin having crystalline properties and the polyester resin having carbon-carbon double bonds to be mixed, based on the unsaturated carboxylic acid component and the unsaturated alcohol component contained in the constituent components of the polyester resin having carbon-carbon double bonds.

[0080] When the amount of the radical reaction initiator used is 0.1 parts by mass or more, the crosslinking reaction tends to proceed easily, and when the amount is 10.0 parts by mass or less, the odor tends to be satisfactory. The amount used is more preferably 0.3 to 8.0 parts by mass, and further preferably 0.5 to 5.0 parts by mass.

[0081] The amount of carbon-carbon double bonds in the toner is not particularly limited, but is preferably 0.50 mmol / g or less, more preferably 0.40 mmol / g or less, and further preferably 0.30 mmol / g or less based on the mass of the toner.

[0082] In the case of the above range, the charge leakage of the toner is alleviated and the charging performance is stabilized.

[0083] The lower limit is not particularly limited, but is preferably 0.10 mmol / g or more, and more preferably 0.20 mmol / g or more.

[0084] The crystalline portion is preferably a crystalline vinyl resin portion. The crystalline vinyl resin portion is preferably a polymer A1 portion, which is a polymer comprising a polymerizable monomer A1. The polymerizable monomer A1 is a (meth)acrylate having a chain hydrocarbon group having 18 to 36 carbon atoms. The mass ratio of the polymerizable monomer A1 units in the polymer A1 portion is preferably 30% to 99% by mass.

[0085] When the mass ratio is 30% by mass or more, low-temperature fixing property is improved, and when the mass ratio is 99% by mass or less, hot offset resistance is improved. In addition, from the viewpoint of achieving low-temperature fixing property as well as hot offset resistance and heat-resistant storage stability, the mass ratio is more preferably 50% by mass to 98% by mass, further preferably 55% by mass to 97% by mass, and even more preferably 60% by mass to 95% by mass.

[0086] When the carbon number of the chain hydrocarbon group of the polymerizable monomer A1 is 18 or more, the melting point of the crystalline portion is increased and the heat-resistant storage stability of the toner is improved. When the carbon number is 36 or less, the melting point is appropriate and thus the low-temperature fixing property is improved.

[0087] The amorphous site is a non-crystalline modified resin site in which a crystalline vinyl resin and a polyester resin are cross-linked via carbon-carbon bonds. This site comprises a site derived from a crystalline vinyl resin and a polyester site. Of the amorphous sites, the site derived from a crystalline vinyl resin is preferably a polymer A2 site, which is a polymer composed of a monomer comprising polymerizable monomer A2. Polymerizable monomer A2 is a (meth)acrylate having a chain hydrocarbon group having 18 to 36 carbon atoms.

[0088] From the perspective of promoting block polymer formation, the crystalline vinyl resin moiety (i.e., polymer A2 moiety) in the modified resin moiety (cross-linked polyester resin moiety), which is an amorphous moiety, and the crystalline vinyl resin moiety (i.e., polymer A1 moiety) in the crystalline moiety preferably have the same structure. Specifically, the crystalline vinyl resin moiety in the modified resin moiety, which is an amorphous moiety, is preferably derived from polymer A1, which is a polymer containing monomers of polymerizable monomer A1.

[0089] The polymerizable monomer A1 is a (meth)acrylate having a chain hydrocarbon group having 18 to 36 carbon atoms, and the mass ratio of the polymerizable monomer A1 unit in the polymer A1 portion is preferably 30 to 99 mass%. Similarly, the mass ratio of the polymerizable monomer A2 unit in the polymer A2 portion is also preferably 30 to 99 mass%.

[0090] Examples of the chain hydrocarbon group having 18 to 36 carbon atoms include chain unsaturated hydrocarbon groups having 18 to 36 carbon atoms and chain saturated hydrocarbon groups (hereinafter also referred to as alkyl groups) having 18 to 36 carbon atoms. Among the (meth)acrylates having a chain hydrocarbon group having 18 to 36 carbon atoms, (meth)acrylates having an alkyl group having 18 to 36 carbon atoms are preferred.

[0091] Examples of the (meth)acrylate having an alkyl group having 18 to 36 carbon atoms include (meth)acrylates having a linear alkyl group having 18 to 36 carbon atoms [octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosyl (meth)acrylate, behenyl (meth)acrylate, tetracosyl (meth)acrylate, hexacosyl (meth)acrylate, montanyl (meth)acrylate, triacontyl (meth)acrylate, and docosyl (meth)acrylate, etc.] and (meth)acrylates having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.].

[0092] Among them, from the viewpoint of improving the storage stability, low-temperature fixing property and hot offset resistance of the toner, (meth)acrylates having an alkyl group having 18 to 34 carbon atoms are preferred, and (meth)acrylates having an alkyl group having 18 to 30 carbon atoms are more preferred, and at least one selected from the group consisting of stearyl (meth)acrylate, octadecyl (meth)acrylate and behenyl (meth)acrylate is even more preferred.

[0093] The polymerizable monomer A (polymerizable monomer A1 and polymerizable monomer A2 are collectively referred to as polymerizable monomer A) can be used alone or in combination of two or more.

[0094] In addition to the polymerizable monomer A, the monomers used for the synthesis of the polymer A (polymer A1 and polymer A2 are collectively referred to as polymer A) may further include at least one polymerizable monomer B selected from the group consisting of styrene, methyl methacrylate, and methyl acrylate.

[0095] Among these polymerizable monomers B, styrene is preferable from the viewpoints of low-temperature fixing ability, heat-resistant storage stability, and pulverizability of the binder resin.

[0096] The mass ratio of the polymerizable monomer B unit in polymer A is preferably 2% to 35% by mass, and more preferably 4% to 25% by mass. In addition, the mass ratio of the polymerizable monomer B unit in the polymer A site (polymer A1 site and polymer A2 site are collectively referred to as polymer A site) is also preferably 2% to 35% by mass, and more preferably 4% to 25% by mass.

[0097] In addition to the polymerizable monomer A and the polymerizable monomer B, the monomers used for the synthesis of the polymer A may include a polymerizable monomer C. From the viewpoint of controlling the crystallinity of the crystalline site to control the heat-resistant storage stability and low-temperature fixing properties of the toner, it is preferable to include the polymerizable monomer C. In addition, by using the polymerizable monomer C as a constituent monomer, the glass transition temperature and elasticity of the non-crystalline site can be controlled, and the hot offset resistance of the toner can be improved.

[0098] For example, the following monomers can be used as the polymerizable monomer C. The polymerizable monomer C can be used alone or in combination of two or more.

[0099] The mass ratio of the polymerizable monomer C unit in polymer A is preferably 2% to 35% by mass, and more preferably 4% to 25% by mass. The mass ratio of the polymerizable monomer C unit in the polymer A site is also preferably 2% to 35% by mass, and more preferably 4% to 25% by mass.

[0100] Monomers having a nitrile group: for example, acrylonitrile and methacrylonitrile.

[0101] Monomers having a hydroxyl group: for example, 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate.

[0102] Monomer having an amide group: for example, acrylamide, and monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having an ethylenically unsaturated bond and having 2 to 30 carbon atoms (acrylic acid, methacrylic acid, etc.) by a known method.

[0103] Monomers having a carbamate group: For example, by reacting an alcohol having an ethylenically unsaturated bond and having 2 to 22 carbon atoms (2-hydroxyethyl methacrylate and vinyl alcohol, etc.) with an isocyanate having 1 to 30 carbon atoms [monoisocyanate compounds (benzenesulfonyl isocyanate, toluenesulfonyl isocyanate, phenyl isocyanate, p-chlorophenyl isocyanate, butyl isocyanate, hexyl isocyanate, tert-butyl isocyanate, cyclohexyl isocyanate, isocyanate], Octyl cyanate, 2-ethylhexyl isocyanate, dodecyl isocyanate, adamantyl isocyanate, 2,6-dimethylphenyl isocyanate, 3,5-dimethylphenyl isocyanate, 2,6-dipropylphenyl isocyanate, etc.), aliphatic diisocyanate compounds (trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate ester, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate, etc.), alicyclic diisocyanate compounds (1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylene diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylxylene diisocyanate, etc.), and aromatic a monomer obtained by reacting a diisocyanate compound (phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylene diisocyanate, etc.), and

[0104] By reacting alcohols having 1 to 26 carbon atoms (methanol, ethanol, propanol, isopropanol, butanol, tert-butanol, amyl alcohol, heptanol, octanol, 2-ethylhexanol, nonanol, decanol, undecanol, lauryl alcohol, dodecanol, myristyl alcohol, pentadecanol, cetyl alcohol, heptadecanol, stearyl alcohol, isostearyl alcohol, trans-octadecenol, oleyl alcohol, linoleyl alcohol, linolenic alcohol, nonadecanol, heneicosyl alcohol, behenyl alcohol, and erucyl alcohol) by known methods, Monomers obtained by reacting an ethylenically unsaturated bond and an isocyanate having 2 to 30 carbon atoms [such as 2-isocyanatoethyl (meth)acrylate, 2-(O-[1'-methylpropylideneamino]carboxyamino)ethyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, and 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate], etc.

[0105] Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amines (n-butylamine, tert-butylamine, propylamine, isopropylamine, etc.), secondary amines (di-n-ethylamine, di-n-propylamine, di-n-butylamine, etc.), aniline, cyclohexylamine, etc.] with an isocyanate having an ethylenically unsaturated bond and having 2 to 30 carbon atoms by a known method.

[0106] Monomers having a carboxyl group: for example, methacrylic acid, acrylic acid, and 2-carboxyethyl (meth)acrylate.

[0107] Among these, monomers having a nitrile group, an amide group, a carbamate group, a hydroxyl group, or a urea group are preferably used. More preferably, monomers having an ethylenically unsaturated bond and at least one functional group selected from the group consisting of a nitrile group, an amide group, a carbamate group, a hydroxyl group, and a urea group are used. Particularly preferably, at least one monomer selected from the group consisting of acrylonitrile and methacrylonitrile is used.

[0108] In addition, as the polymerizable monomer C, vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl octanoate, vinyl decanoate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate and vinyl octanoate are also preferably used.

[0109] Vinyl esters are non-conjugated monomers and easily maintain the reactivity with the first polymerizable monomer at an appropriate level, thereby easily improving the crystallinity of the crystalline portion of the polymer A and making it easier to achieve both low-temperature fixability and heat-resistant storage stability.

[0110] Examples of the polymerizable monomer C may further include at least one selected from the group consisting of the following formulae (A) and (B).

[0111]

[0112] In the formula, X represents a single bond or an alkylene group having 1 to 6 carbon atoms,

[0113] R 1 is a nitrile group (-C≡N),

[0114] Amide (-C(=O)NHR 10 (R 10 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms)),

[0115] Hydroxyl,

[0116] -COOR 11 (R 11 is an alkyl group having 1 to 6 (preferably 1 to 4) carbon atoms or a hydroxyalkyl group having 1 to 6 (preferably 1 to 4) carbon atoms),

[0117] Carbamate group (-NHCOOR 12 (R 12 is an alkyl group having 1 to 4 carbon atoms)),

[0118] Urea group (-NH-C(=O)-N(R 13 )2(R 13 are independently a hydrogen atom or an alkyl group having 1 to 6 (preferably 1 to 4) carbon atoms)),

[0119] -COO(CH2)2NHCOOR 14 (R 14 is an alkyl group having 1 to 4 carbon atoms), or

[0120] -COO(CH2)2-NH-C(=O)-N(R 15 )2(R 15 are independently a hydrogen atom or an alkyl group having 1 to 6 (preferably 1 to 4) carbon atoms), and

[0121] R 2 is an alkyl group having 1 to 4 carbon atoms, and R 3 are independently a hydrogen atom or a methyl group.

[0122] The vinyl resin having crystallinity can be preferably produced by polymerizing a monomer composition containing polymerizable monomers A, B, and C. For example, the vinyl resin can be synthesized by a solution polymerization method in which polymerizable monomers are reacted with a radical reaction initiator in a solvent (toluene, etc.).

[0123] When the vinyl resin having crystallinity contains THF-insoluble matter, the amount of the THF-insoluble matter is preferably 1.0% by mass or less, and more preferably 0.1% by mass to 1.0% by mass.

[0124] Furthermore, from the viewpoint of low-temperature fixing ability, it is preferred that the vinyl resin having crystallinity does not contain THF-insoluble matter.

[0125] The number average molecular weight Mn of the THF-soluble matter of the crystalline vinyl resin is preferably 1000 to 300,000, more preferably 3000 to 50,000, and even more preferably 5000 to 20,000 from the viewpoint of achieving both heat-resistant storage stability and low-temperature fixability of the toner.

[0126] The weight average molecular weight Mw is preferably from 10,000 to 500,000, more preferably from 20,000 to 100,000, and further preferably from 40,000 to 80,000.

[0127] A cross-linked polyester resin is a modified resin having a structure in which a crystalline vinyl resin and a polyester resin are cross-linked via carbon-carbon bonds. A cross-linked polyester resin also has a structure in which the polyester resin is cross-linked via carbon-carbon bonds. A carbon-carbon bond means that at least one bond forming the cross-linked structure is a direct bond between carbon atoms.

[0128] The polyester resins mentioned herein are not particularly limited as long as they can form crosslinks through carbon-carbon bonds. Among such resins, polyester resins having carbon-carbon double bonds are preferred from the viewpoint of easily forming a crosslinked structure.

[0129] Furthermore, it is preferred that at least a portion of the carbon-carbon bonds of the cross-linked polyester resin be carbon-carbon bonds in which carbon-carbon double bonds derived from the polyester resin having carbon-carbon double bonds are cross-linked.

[0130] The cross-linked polyester resin is obtained by reacting the carbon-carbon double bonds of a polyester resin having carbon-carbon double bonds. The cross-linked polyester resin can also be obtained by cross-linking by abstracting hydrogen atoms bonded to carbon atoms contained in the polyester resin having carbon-carbon double bonds through a hydrogen abstraction reaction induced by heating or the like.

[0131] Here, the cross-linked polyester resin is a polyester resin having a branch (cross-linking point) in the main chain. Specifically, it refers to a polyester resin obtained by a cross-linking reaction, and examples of the form of the cross-linking reaction include the following.

[0132] Cross-linking reaction to form carbon-carbon bonds (a reaction in which an unsaturated double bond is introduced into the main chain or side chain of a polyester resin, and the unsaturated double bond is reacted by a free radical addition reaction, a cationic addition reaction, or an anionic addition reaction to form an intermolecular carbon-carbon bond; or a reaction in which an intermolecular carbon-carbon bond is formed by a hydrogen atom abstraction reaction using a peroxide or the like; etc.); a reaction in which a cross-linking reaction is produced through an ester bond by a condensation reaction using a trifunctional or higher polycarboxylic acid and a trifunctional or higher polyol; and a polyaddition reaction of a compound containing a polyvalent epoxy group, a polyvalent isocyanate group, a polyvalent carbodiimide group, a polyvalent aziridine group, or a polyvalent oxazoline group, etc., with a polyester resin; etc.

[0133] Furthermore, the cross-linked polyester resin may have cross-linking via carbon-carbon bonds, cross-linking via ester bonds, cross-linking via addition polymerization, etc. Furthermore, the cross-linked polyester resin may be composed of one cross-linked polyester resin, or may be a mixture of two or more cross-linked polyester resins.

[0134] A cross-linked polyester resin that forms a network by branching is generally insoluble in THF. Therefore, the nonlinearity of the cross-linked polyester resin can be confirmed by whether the cross-linked polyester resin is soluble in THF and has a component that is insoluble in THF (THF-insoluble matter).

[0135] Furthermore, in the toner, the polyester resin having a carbon-carbon double bond is preferably a polycondensate of a carboxylic acid component having at least one of an unsaturated carboxylic acid component and an unsaturated alcohol component and an alcohol component.

[0136] The monomer for the polyester resin having a carbon-carbon double bond may further include a saturated alcohol component or a saturated carboxylic acid component as a constituent component in addition to the unsaturated carboxylic acid component or the unsaturated alcohol component.

[0137] In addition, the polyester resin having a carbon-carbon double bond may be polycondensed using one of the components or may be polycondensed using a plurality of the components together.

[0138] The amount of carbon-carbon double bonds in the polyester resin having carbon-carbon double bonds is not particularly limited, but is preferably 0.02 mmol / g to 0.80 mmol / g, and more preferably 0.20 mmol / g to 0.70 mmol / g.

[0139] In the above range, crosslinking reaction occurs appropriately and block polymerization proceeds moderately, thereby improving the low-temperature fixability and hot offset resistance of the toner and expanding the fixing temperature range. In addition, charge leakage of the toner is reduced and charging performance is stabilized.

[0140] Note that the bonds of the aromatic rings are not considered when determining whether a component is an unsaturated carboxylic acid component or a saturated carboxylic acid component. That is, a compound in which the portion other than the aromatic ring is an unsaturated carboxylic acid is determined to be an unsaturated carboxylic acid component, and a compound in which the portion other than the aromatic ring is a saturated carboxylic acid is determined to be a saturated carboxylic acid component.

[0141] Similarly, the bonds of the aromatic rings are not considered when determining whether a component is an unsaturated alcohol component or a saturated alcohol component. That is, a compound in which the portion other than the aromatic ring is an unsaturated alcohol is determined to be an unsaturated alcohol component, and a compound in which the portion other than the aromatic ring is a saturated alcohol is determined to be a saturated alcohol component.

[0142] The peak top molecular weight Mp of the cross-linked polyester resin is preferably 2000 to 30,000, more preferably 3000 to 20,000, and further preferably 4000 to 12,000. When the peak top molecular weight Mp is within the above range, glossiness, low-temperature fixing property, and hot offset resistance are improved.

[0143] From the viewpoint of charge stability, the acid value of the crosslinked polyester resin is preferably 0 to 30 mg KOH / g, more preferably 0 to 25 mg KOH / g, further preferably 0 to 10 mg KOH / g, and particularly preferably 0.1 to 10 mg KOH / g.

[0144] Furthermore, there is no particular limitation on the method for producing the polyester resin having a carbon-carbon double bond. As described above, a polyester resin obtained by polycondensing constituent components containing one or more unsaturated carboxylic acid components and / or unsaturated alcohol components is preferred.

[0145] Furthermore, examples of methods that can be used when the polyester is non-linear include a method of using a trivalent or higher polyol as a saturated alcohol component as a constituent component in addition to the unsaturated carboxylic acid component and / or the unsaturated alcohol component, and a method of using a trivalent or higher carboxylic acid, or an anhydride thereof, or a lower alkyl ester thereof as a saturated carboxylic acid component in addition to the unsaturated carboxylic acid component and / or the unsaturated alcohol component.

[0146] For example, the constituent components can be reacted in an atmosphere of an inert gas (nitrogen etc.) at a reaction temperature of preferably 150° C. to 280° C., more preferably 160° C. to 250° C., still more preferably 170° C. to 235° C. From the viewpoint of allowing the polycondensation reaction to proceed reliably, the reaction time is preferably 30 minutes or more, and more preferably 2 hours to 40 hours.

[0147] Furthermore, an esterification catalyst may be used as needed.

[0148] Examples of esterification catalysts include tin-containing catalysts (e.g., dibutyltin oxide, etc.), antimony dioxide, titanium-containing catalysts (e.g., titanium alkoxide, potassium oxalate titanate, titanium terephthalate, titanium terephthalate alkoxide, dihydroxybis(triethanolamine)titanium, monohydroxytris(triethanolamine)titanium, titanyl-bis(triethanolamine), and intramolecular condensation products thereof, etc.; titanium tributoxyterephthalate, titanium triisopropoxyterephthalate, and titanium diisopropoxyditerephthalate, etc.), zirconium-containing catalysts (e.g., zirconyl acetate, etc.), and zinc acetate, etc.

[0149] Among them, titanium-containing catalysts are preferred. The titanium-containing catalysts are also effective in reducing pressure and thus increasing the reaction rate at the end of the reaction.

[0150] Furthermore, a stabilizer may be added for the purpose of achieving polymerization stability. Examples of the stabilizer include hydroquinone, methylhydroquinone, and hindered phenol compounds.

[0151] The total addition ratio of the saturated alcohol component and the unsaturated alcohol component to the unsaturated carboxylic acid component and the saturated carboxylic acid component to be used for the reaction is preferably 2.0 / 1.0 to 1.0 / 2.0, more preferably 1.5 / 1.0 to 1.0 / 1.3, and still more preferably 1.4 / 1.0 to 1.0 / 1.2 in terms of the equivalent ratio of hydroxyl groups to carboxyl groups ([OH] / [COOH]). In addition, it is sufficient to include one or both of the unsaturated carboxylic acid component and the unsaturated alcohol component.

[0152] Examples of the unsaturated alcohol component include monohydric alcohols, diols, and the like.

[0153] Examples of the monohydric alcohol include unsaturated monohydric alcohols having 2 to 30 carbon atoms, and preferred examples include 2-propylene-1-ol, oleyl alcohol, 2-hydroxyethyl methacrylate, etc. Examples of the diol include unsaturated diols having 2 to 30 carbon atoms, and ricinoleyl alcohol is a preferred example.

[0154] Examples of the saturated alcohol component include monohydric alcohols, diols, and polyols having 3 to 8 or more hydroxyl groups, etc. These may be used alone or in combination of two or more.

[0155] Examples of the monohydric alcohol include alkanols having 1 to 30 carbon atoms (methanol, ethanol, isopropyl alcohol, dodecanol, myristyl alcohol, cetyl alcohol, stearyl alcohol, behenyl alcohol, and the like) and the like.

[0156] Among these monohydric alcohols, alkanols having 8 to 24 carbon atoms are preferred, and dodecanol, myristyl alcohol, stearyl alcohol, and behenyl alcohol are more preferred.

[0157] Examples of the diol include alkylene glycols having 2 to 36 carbon atoms (ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, etc.); alkylene ether glycols having 4 to 86 carbon atoms (diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, etc.); Alicyclic diols of 6 to 36 carbon atoms (such as 1,4-cyclohexanedimethanol and hydrogenated bisphenol A), (poly)oxyalkylenes of the above-mentioned alicyclic diols [the number of carbon atoms in the alkylene group is 2 to 4 (such as ethylene oxide and propylene oxide), which also applies to the following polyoxyalkylene] ethers [the number of alkylene oxide units is 1 to 30]; diphenols [monocyclic diphenols (such as hydroquinone)] and polyoxyalkylene ethers of bisphenols (the number of alkylene oxide units is 2 to 30), etc.

[0158] Among these diols, alkylene glycols having 2 to 36 carbon atoms and polyoxyalkylene ethers of bisphenols are preferred from the viewpoint of low-temperature fixing property and heat-resistant storage stability, and polyoxyalkylene ethers of bisphenols are more preferred. Polyoxyalkylene ethers of bisphenols are obtained by adding alkylene oxide to bisphenols. Examples of bisphenols include those represented by the following formula (5):

[0159] HO-Ar-X-Ar-OH (5)

[0160] In the formula, X represents an alkylene group having 1 to 3 carbon atoms, -SO2-, -O-, -S- or a direct bond, and Ar each independently represents an unsubstituted phenylene group or a phenylene group having a substituent, and has a halogen atom or an alkyl group having 1 to 30 carbon atoms as a substituent.

[0161] Examples of bisphenols include bisphenol A, bisphenol F, bisphenol B, bisphenol AD, bisphenol S, trichlorobisphenol A, tetrachlorobisphenol A, dibromobisphenol F, 2-methylbisphenol A, 2,6-dimethylbisphenol A, 2,2′-diethylbisphenol F, and the like, and these may be used in combination of two or more.

[0162] The alkylene oxide added to these bisphenols is preferably an alkylene oxide having 2 to 4 carbon atoms, and specifically, ethylene oxide, propylene oxide (meaning "1,2-propylene oxide"), 1,2-butylene oxide, 2,3-butylene oxide, 1,3-butylene oxide or isobutylene oxide, tetrahydrofuran, and combinations of two or more thereof, and the like.

[0163] Among them, ethylene oxide and propylene oxide are preferred. The number of added moles of the alkylene oxide is preferably 2 to 30 moles, and more preferably 2 to 10 moles.

[0164] Among the polyoxyalkylene ethers of bisphenols, ethylene oxide adducts and propylene oxide adducts of bisphenol A (average addition mole number of 2 to 4, preferably 2 or 3) are preferred from the viewpoints of toner fixing performance, pulverizability and heat-resistant storage stability.

[0165] Examples of the polyol having 3 to 8 or more hydroxyl groups include aliphatic polyols having 3 to 8 or more hydroxyl groups and having 3 to 36 carbon atoms, sugars and derivatives thereof, (poly)oxyalkylene ethers of aliphatic polyols (the number of alkylene oxide units is 1 to 30), polyoxyalkylene ethers of trisphenols (trisphenol PA, etc.) (the number of alkylene oxide units is 2 to 80), and polyoxyalkylene ethers of novolac resins (phenol novolac and cresol novolac, etc.; the average degree of polymerization is 3 to 60) (the number of alkylene oxide units is 2 to 30), etc.

[0166] Examples of the aliphatic polyol having 3 to 8 or more hydroxyl groups and having 3 to 86 carbon atoms include alkanepolyols and intramolecular or intermolecular dehydration products thereof, and more specifically, glycerol, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, polyglycerol, dipentaerythritol, and the like.

[0167] Specific examples of sugars and their derivatives include sucrose, methyl glucoside, and the like.

[0168] Among the polyols having 3 to 8 or more hydroxyl groups, aliphatic polyols having 3 to 8 or more hydroxyl groups and having 3 to 36 carbon atoms and polyoxyalkylene ethers (the number of alkylene oxide units is 2 to 30) of novolac resins (phenol novolac, cresol novolac, etc.) are preferred from the viewpoint of achieving both low-temperature fixing ability and hot offset resistance.

[0169] Among the saturated alcohol components, from the viewpoint of improving low-temperature fixing ability, hot offset resistance and heat-resistant storage stability, alkylene glycols having 2 to 36 carbon atoms, polyoxyalkylene ethers of bisphenols (the number of alkylene oxide units is 2 to 30), aliphatic polyols having 3 to 36 carbon atoms and 3 to 8 or more hydroxyl groups, and polyoxyalkylene ethers of novolac resins (the number of alkylene oxide units is 2 to 30) are preferred.

[0170] From the viewpoint of heat-resistant storage stability, more preferred saturated alcohol components are alkylene glycols having 2 to 10 carbon atoms, polyoxyalkylene ethers of bisphenols (having 2 to 5 alkylene oxide units), aliphatic polyols having 3 to 8 or more hydroxyl groups, and polyoxyalkylene ethers of novolac resins (the number of alkylene oxide units is 2 to 30).

[0171] Particularly preferred are alkylene glycols having 2 to 6 carbon atoms, polyoxyalkylene ethers of bisphenol A (the number of alkylene oxide units is 2 to 5), and trivalent aliphatic polyols. Most preferred are ethylene glycol, propylene glycol, polyoxyalkylene ethers of bisphenol A (the number of alkylene oxide units is 2 or 3), and trimethylolpropane.

[0172] Examples of the unsaturated carboxylic acid component include unsaturated monocarboxylic acids, unsaturated dicarboxylic acids, unsaturated polycarboxylic acids, anhydrides and lower alkyl esters of these acids, and the like.

[0173] The unsaturated monocarboxylic acid includes unsaturated monocarboxylic acids having 2 to 80 carbon atoms, and specifically, acrylic acid, methacrylic acid, propiolic acid, 2-butenoic acid, crotonic acid, isocrotonic acid, 3-butenoic acid, angelic acid, tiliac acid, 4-pentenoic acid, 2-ethyl-2-butenoic acid, 10-undecenoic acid, 2,4-hexadienoic acid, myristoleic acid, palmitoleic acid, hexadecenoic acid, oleic acid, elaidic acid, vaccenic acid, gadoleic acid, erucic acid, nervonic acid, and the like.

[0174] The unsaturated dicarboxylic acid includes olefin dicarboxylic acids having 4 to 50 carbon atoms, and specifically, alkenyl succinic acid such as dodecenyl succinic acid, maleic acid, fumaric acid, citraconic acid, mesaconic acid, itaconic acid, glutaconic acid, and the like.

[0175] Examples of the unsaturated polycarboxylic acid include vinyl polymers of unsaturated carboxylic acids (having a number average molecular weight Mn of 450 to 10,000 as measured by gel permeation chromatography (GPC)).

[0176] Among these unsaturated carboxylic acids, acrylic acid, methacrylic acid, alkenyl succinic acids such as dodecenyl succinic acid, maleic acid, and fumaric acid are preferred from the viewpoint of achieving both low-temperature fixability and hot offset resistance. More preferred are acrylic acid, methacrylic acid, maleic acid, fumaric acid, and combinations thereof. Furthermore, the unsaturated carboxylic acid may be an anhydride or a lower alkyl ester of these acids.

[0177] Examples of the saturated carboxylic acid component include aliphatic carboxylic acids having 2 to 50 carbon atoms (stearic acid, behenic acid, etc.), aromatic carboxylic acids having 7 to 37 carbon atoms (benzoic acid, etc.), alkanedicarboxylic acids having 2 to 50 carbon atoms (oxalic acid, malonic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, etc.), aromatic dicarboxylic acids having 8 to 86 carbon atoms (phthalic acid, isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, etc.), aromatic polycarboxylic acids having 9 to 20 carbon atoms (trimellitic acid, pyromellitic acid, etc.), and aliphatic tricarboxylic acids having 6 to 36 carbon atoms (hexanetricarboxylic acid, etc.).

[0178] Furthermore, the saturated carboxylic acid component may be an anhydride or a lower alkyl (1 to 4 carbon atoms) ester (methyl ester, ethyl ester, isopropyl ester, etc.) of any of these carboxylic acids.

[0179] Among these saturated carboxylic acid components, aromatic carboxylic acids having 7 to 87 carbon atoms, alkanedicarboxylic acids having 2 to 50 carbon atoms, aromatic dicarboxylic acids having 8 to 20 carbon atoms, and aromatic polycarboxylic acids having 9 to 20 carbon atoms are preferred from the viewpoint of achieving low-temperature fixability, hot offset resistance, and heat-resistant storage stability.

[0180] From the viewpoint of heat-resistant storage stability and charging properties, benzoic acid, adipic acid, alkylsuccinic acid, terephthalic acid, isophthalic acid, trimellitic acid, pyromellitic acid, and combinations thereof are more preferred.

[0181] Particularly preferred are adipic acid, terephthalic acid, trimellitic acid and combinations thereof. In addition, anhydrides or lower alkyl esters of these acids may also be used.

[0182] The glass transition temperature (Tg) of the THF-insoluble matter of the resin component of the toner is preferably 25° C. to 55° C., and more preferably 30° C. to 53° C. When the Tg is 25° C. or higher, the heat-resistant storage stability of the toner is improved. When the Tg is 55° C. or lower, the non-crystalline portion is easily plasticized in the fixing step, and the low-temperature fixing property is improved.

[0183] In a temperature increase measurement of the toner using a constant load extrusion rheometer, the softening point (1 / 2 outflow temperature) is preferably 80° C. to 130° C., and more preferably 85° C. to 128° C. When the softening point is 80° C. or higher, hot offset resistance becomes satisfactory. When the temperature is 130° C. or lower, low-temperature fixing property is significantly improved.

[0184] Furthermore, in the viscoelasticity measurement of the tetrahydrofuran-soluble matter of the toner, it is preferable that the storage elastic modulus Gk'(50) at 50° C. satisfies the following formula (6).

[0185] G'(50)≥1.0×107 Pa (6)

[0186] G'(50) is more preferably 1.5×10 7 Pa or more, and more preferably 2.0×10 7 Pa or more. The upper limit is not particularly limited, but is preferably 1.0×10 10 Below Pa.

[0187] In the case where G'(50) is within this range, the melting point and glass transition point of the toner are sufficient, and the storage stability is satisfactory. G'(50) can be controlled by the molecular weight of the binder resin.

[0188] Furthermore, in the viscoelasticity measurement of the tetrahydrofuran-soluble matter of the toner, it is preferable that the storage elastic modulus G′(100) at 100° C. satisfies the following formula (7).

[0189] G'(100)≤1.0×10 6 Pa (7)

[0190] G'(100) is more preferably 0.9×10 6 Pa or less, and more preferably 0.8×10 6 Pa or less. The lower limit is not particularly limited, but is preferably 1.0×10 3 Pa and above.

[0191] A higher storage elastic modulus of the toner at high temperature can suppress density unevenness during fixing. Therefore, in the viscoelasticity measurement of the tetrahydrofuran-soluble matter of the toner, the storage elastic modulus G'(150) at 150°C is preferably 1.0×10 4 Pa to 1.0×10 7 Pa.

[0192] The storage elastic modulus at 150°C is more preferably 0.8×10 5 Pa or more, and more preferably 1.0×10 5 Pa or more. The upper limit is not particularly limited, but is preferably 1.0×10 7 Pa or less, and more preferably 1.0×10 6 Pa or less. This value can be controlled by the molecular weight, THF-insoluble matter ratio, and Tg of the binder resin.

[0193] When the toner is subjected to heat sufficient to melt the toner from the outside, the viscoelasticity of the toner decreases, but it is speculated that the storage elastic modulus maintained at a constant value at high temperatures means that the highly elastic substance that becomes the THF-insoluble substance in the toner maintains constant viscoelasticity of the entire toner.

[0194] In addition to the binder resin, the toner may optionally include one or more known additives selected from a colorant, a release agent, a charge control agent, a fluidizing agent, etc. Materials other than the binder resin used for the toner particles will be specifically described below.

[0195] The toner may contain a releasing agent to impart releasability during fixing. Examples of the releasing agent include polyolefin copolymers, polyolefin waxes, microcrystalline waxes, paraffin waxes, aliphatic hydrocarbon waxes such as Fischer-Tropsch waxes, and ester waxes.

[0196] The molecular weight of the release agent is preferably 1000 or greater. A molecular weight of 1000 or greater reduces compatibility with the crystalline site, leading to phase separation. As a result, the release agent is more likely to seep onto the toner particle surface during fixing, improving releasability. Furthermore, since the crystalline site and the release agent are less likely to be compatible with each other, the crystallinity of the crystalline site is improved, raising the melting point and thus improving heat-resistant storage stability.

[0197] Here, the molecular weight of the releasing agent refers to the peak molecular weight (Mp) in gel permeation chromatography (GPC) measurement. The measurement method will be described later.

[0198] The molecular weight of the releasing agent is preferably 1500 or more. There is no particular limitation on the upper limit, but from the viewpoint of ensuring releasability, the molecular weight is preferably 10,000 or less, and more preferably 5000 or less.

[0199] The releasing agent is not particularly limited as long as the molecular weight is 1000 or more, and examples thereof include the following.

[0200] Aliphatic hydrocarbon-based wax: low molecular weight polyethylene, low molecular weight polypropylene, low molecular weight olefin copolymer, Fischer-Tropsch wax, or a wax obtained by oxidizing the same and adding an acid thereto.

[0201] Furthermore, ester wax containing fatty acid ester as a main component can also be used. From the viewpoint of molecular weight, the ester wax is preferably a trifunctional or higher ester wax, and more preferably a tetrafunctional or higher ester wax.

[0202] For example, a trifunctional or higher functional ester wax is obtained by condensing a trifunctional or higher functional acid with a long-chain linear saturated alcohol or by synthesizing a trifunctional or higher functional alcohol and a long-chain linear saturated fatty acid.

[0203] Examples of trifunctional or higher alcohols that can be used for the ester wax include the following, but are not limited thereto: A plurality of ester waxes may be mixed and used.

[0204] Glycerol, trimethylolpropane, erythritol, pentaerythritol, sorbitol. In addition, condensation products include so-called polyglycerols such as diglycerol, triglycerol, tetraglycerol, hexaglycerol, and decaglycerol obtained by condensation of glycerol, di(trimethylol)propane and tri(trimethylol)propane obtained by condensation of trimethylolpropane, and dipentaerythritol and tripentaerythritol obtained by condensation of pentaerythritol.

[0205] Among them, a structure having a branched structure is preferable, pentaerythritol or dipentaerythritol is more preferable, and dipentaerythritol is particularly preferable.

[0206] Long-chain linear saturated fatty acids are represented by the general formula C n H 2n+1 COOH, and acids wherein n is 5 to 28 are preferably used.

[0207] The following examples may be mentioned, but these examples are not limiting. In some cases, the acid may be used as a mixture. Hexanoic acid, caprylic acid, octylic acid, nonanoic acid, decanoic acid, dodecanoic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid and behenic acid. From the perspective of the melting point of the wax, myristic acid, palmitic acid, stearic acid and behenic acid are preferred.

[0208] Examples of trifunctional or higher functional acids include trimellitic acid and butanetetracarboxylic acid, but these examples are not limitative. In some cases, the acids may be used as a mixture.

[0209] Long chain linear saturated alcohols are composed of C n H 2n+1 OH represents, and alcohols wherein n is 5 to 28 are preferably used.

[0210] The following examples may be mentioned, but these examples are not limiting. In some cases, the alcohol may be used as a mixture. Caprylic alcohol, lauryl alcohol, myristyl alcohol, palmityl alcohol, stearyl alcohol, and behenyl alcohol. From the perspective of the melting point of the wax, myristyl alcohol, palmityl alcohol, stearyl alcohol, and behenyl alcohol are preferred.

[0211] A releasing agent having a softening point of 50 to 170° C. as measured by a flow tester is preferable, and examples thereof include polyolefin wax, natural wax, aliphatic alcohol having 30 to 50 carbon atoms, fatty acid having 30 to 50 carbon atoms, and mixtures thereof.

[0212] Examples of polyolefin waxes include (co)polymers of olefins (e.g., ethylene, propylene, 1-butene, isobutylene, 1-hexene, 1-dodecene, 1-octadecene, and mixtures thereof, etc.) [including those obtained by (co)polymerization and thermally reduced polyolefins], oxides of olefin (co)polymers obtained using oxygen and / or ozone, maleic acid-modified products of olefin (co)polymers [e.g., products obtained by modification with maleic acid and its derivatives (maleic anhydride, monomethyl maleate, monobutyl maleate, dimethyl maleate, etc.)], copolymers of olefins with unsaturated carboxylic acids [(meth)acrylic acid, itaconic acid, maleic anhydride, etc.] and / or unsaturated carboxylic acid alkyl esters [alkyl (meth)acrylate (alkyl having 1 to 18 carbon atoms) esters and alkyl maleate (alkyl having 1 to 18 carbon atoms) esters, etc.], and sasol wax, etc.

[0213] Examples of natural waxes include carnauba wax, montan wax, paraffin wax, and rice wax. Triacontanol is an example of an aliphatic alcohol having 30 to 50 carbon atoms. Triacontanic acid is an example of a fatty acid having 30 to 50 carbon atoms.

[0214] The release agent preferably includes an aliphatic hydrocarbon wax, and more preferably an aliphatic hydrocarbon wax. Since the aliphatic hydrocarbon wax has low polarity, such wax easily bleeds out from the polymer A during fixing.

[0215] The amount of the release agent in the toner particles is preferably 1.0% to 30.0% by mass, and more preferably 2.0% to 25.0% by mass. When the amount of the release agent in the toner particles is within the above range, releasability during fixing is easily ensured. When the amount is 1.0% by mass or more, the releasability of the toner becomes satisfactory. When the amount is 30.0% by mass or less, the release agent is less likely to be exposed on the surface of the toner particles, and heat-resistant storage stability becomes satisfactory.

[0216] The melting point of the release agent is preferably 80°C to 120°C. When the melting point of the release agent is within the above range, the release agent easily melts during fixing and oozes onto the surface of the toner particles, and releasability is easily exhibited. The melting point is more preferably 85°C to 110°C. When the melting point is 80°C or higher, the release agent is less likely to be exposed on the surface of the toner particles, and heat-resistant storage stability becomes satisfactory. Meanwhile, when the melting point is 120°C or lower, the release agent melts appropriately during fixing, improving low-temperature fixing properties and offset resistance.

[0217] The acid value of the release agent is preferably 5.0 mg KOH / g to 20.0 mg KOH / g. When the acid value is 5.0 mg KOH / g or higher, the release agent has high polarity, which reduces its affinity for long-chain alkyl groups in the crystalline site, facilitates phase separation of the release agent, and improves releasability. Furthermore, when the acid value of the release agent is 20.0 mg KOH / g or lower, the polarity is moderate and the release agent is easily wetted with air, thereby promoting exposure to the surface of the toner particles during melting and improving releasability.

[0218] The acid value of the release agent is determined by AV W The acid value of the non-crystalline part of the binder resin is represented by AV A When the acid value of the release agent is controlled within this range, the dispersibility of the release agent in the non-crystalline part of the binder resin is improved, and the releasability of the toner is easily ensured. More preferably, AV W -AV A It is about 1 to 29.

[0219] AV W >AV A (4)

[0220] The toner may contain magnetic iron oxide particles and be used as a magnetic toner. In this case, the magnetic iron oxide particles may also be used as a colorant.

[0221] Examples of magnetic iron oxide particles include iron oxides such as magnetite, hematite and ferrite, metals such as iron, cobalt and nickel, alloys of these metals with metals such as aluminum, cobalt, copper, lead, magnesium, tin, zinc, antimony, bismuth, calcium, manganese, titanium, tungsten and vanadium, and mixtures thereof.

[0222] The average particle size of these magnetic iron oxide particles is preferably 2 μm or less, and more preferably 0.05 to 0.5 μm. The amount in the toner is preferably 20 to 200 parts by mass, and more preferably 40 to 150 parts by mass, relative to 100 parts by mass of the binder resin.

[0223] A colorant can be used in the toner. Examples of the colorant are given below.

[0224] As the black colorant, for example, carbon black, grafted carbon, or a colorant toned in black by using yellow / magenta / cyan colorants described later can be used.

[0225] Examples of yellow colorants include compounds represented by condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Examples of magenta colorants include condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinones, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Examples of cyan colorants include copper phthalocyanine compounds and their derivatives, anthraquinone compounds, and basic dye lake compounds.

[0226] These colorants can be used alone or in mixtures, and can also be used in a solid solution state. The colorant is selected from the viewpoints of hue angle, saturation, brightness, weather resistance, and dispersibility in the toner. The amount of the colorant is preferably 1 to 20 parts by mass per 100 parts by mass of the binder resin.

[0227] A charge control agent may be used in a toner to stabilize triboelectric charging performance. Charge control agents that control toners to exhibit negative charging performance and those that control toners to exhibit positive charging performance are known. One or more of these types may be used depending on the type and intended use of the toner.

[0228] The following are examples of charge control agents that control toners to exhibit negative charging properties: organic metal complexes (monoazo metal complexes; acetylacetonate metal complexes); metal complexes or metal salts of aromatic hydroxycarboxylic acids or aromatic dicarboxylic acids. Other examples include aromatic mono- and polycarboxylic acids, their metal salts, and anhydrides; esters; and phenol derivatives such as bisphenol.

[0229] The following are examples of charge control agents that control toners to exhibit positive charging properties: nigrosine and modified products using fatty acid metal salts; quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthalenesulfonate and tetrabutylammonium tetrafluoroborate, and their derivatives; onium salts such as phosphonium salts and their lake pigments; triphenylmethane dyes and their lake pigments (examples of color fixing agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide, and ferrocyanide); and metal salts of higher fatty acids.

[0230] Examples of the fluidizing agent include colloidal silica, alumina powder, titanium oxide powder, calcium carbonate powder, and the like.

[0231] There is no particular limitation on the method for producing the toner particles, and, for example, a pulverization method and a so-called polymerization method such as an emulsion polymerization method, a suspension polymerization method, and a dissolution suspension method can be used.

[0232] From the viewpoint of reducing density unevenness during fixing by maintaining viscoelasticity at high temperatures, a pulverization method is preferred because components insoluble at high temperatures can be dispersed throughout the toner. That is, the toner is preferably pulverized toner.

[0233] In the pulverization method, first, a binder resin constituting toner particles and, if necessary, additives such as a colorant, a release agent, and a charge control agent are thoroughly mixed using a mixer such as a Henschel mixer or a ball mill (mixing step). Prior to the mixing step, a step of adding a radical reaction initiator while melt-kneading the binder resin to crosslink the binder resin is preferably performed.

[0234] Next, the obtained mixture is melt-kneaded using a heat kneading machine such as a twin-screw kneading extruder, a heating roller, a kneader or an extruder (melt-kneading step). The melt-kneaded product is cooled and solidified, then pulverized (pulverization step), and classified as needed. As a result, toner particles can be obtained.

[0235] The toner particles can be used as a toner as they are. If necessary, a known fluidizing agent can be sufficiently mixed using a mixer such as a Henschel mixer to obtain a toner.

[0236] Method for measuring the content ratio of each monomer unit in a crystalline vinyl resin

[0237] Pass under the following conditions 1 The content ratios of monomer units derived from various polymerizable monomers in the polymer A were measured by H-NMR.

[0238] Measuring apparatus: FT NMR apparatus JNM-EX400 (manufactured by JEOL Ltd.)

[0239] Measurement frequency: 400MHz

[0240] Pulse condition: 5.0μs

[0241] Frequency range: 10,500Hz

[0242] Number of points: 64 times

[0243] Measurement temperature: 30℃

[0244] Sample: 50 mg of a measurement sample was placed in a sample tube having an inner diameter of 5 mm and dissolved in a thermostatic bath at 40° C. by adding deuterated chloroform (CDCl 3 ) as a solvent, thereby preparing a sample.

[0245] In income 1On the H-NMR chart, from among the peaks attributable to the constituent components derived from the polymerizable monomer A, a peak independent of peaks attributable to constituent components derived from other sources is selected and the integrated value S1 of the peak is calculated.

[0246] Similarly, from among the peaks attributable to the constituent components derived from the monomer unit of the polymerizable monomer B, a peak independent of peaks attributable to constituent components derived from other sources is selected and the integrated value S2 of the peak is calculated.

[0247] Furthermore, from among the peaks attributable to the constituent components derived from the monomer unit of the polymerizable monomer C, a peak independent of peaks attributable to constituent components derived from other sources is selected and the integrated value S3 of the peak is calculated.

[0248] The above integrated values ​​S1, S2, and S3 are used to obtain the content ratio of the monomer units derived from the polymerizable monomer as follows. Here, n1, n2, and n3 are the number of hydrogen atoms in the component to which the peak of interest for each site belongs. M1, M2, and M3 are the molecular weights of each monomer unit.

[0249] The ratio of the monomer unit derived from the polymerizable monomer A (mol %)={(S1 / n1×M1) / ((S1 / n1×M1)+(S2 / n2×M2)+(S3 / n3×M3))}×100.

[0250] Similarly, the ratio of the monomer units derived from the polymerizable monomer B and the polymerizable monomer C is determined in the following manner.

[0251] The ratio of the monomer unit derived from the polymerizable monomer B (mol %)={(S2 / n2×M2) / ((S1 / n1×M1)+(S2 / n2×M2)+(S3 / n3×M3))}×100.

[0252] The ratio of the monomer unit derived from the polymerizable monomer C (mol %)={(S3 / n3×M3) / ((S1 / n1×M1)+(S2 / n2×M2)+(S3 / n3×M3))}×100.

[0253] When a polymerizable monomer containing no hydrogen atoms as a constituent other than vinyl groups is used in polymer A, 13 C-NMR sets the measured nucleus as 13 C, measured in single pulse mode and with 1 The calculation was performed in the same manner as that of H-NMR.

[0254] Method for measuring the ratio of tetrahydrofuran (THF)-insoluble matter of a resin component

[0255] A total of 1.5 g of toner for measuring the amount of THF-insoluble matter (0.7 g when measuring the THF-insoluble matter of only the resin) is accurately weighed (W1 [g]) and placed on a cylindrical filter paper (trade name: No. 86R, size 28×100 mm, manufactured by Advantech Toyo Co., Ltd.) that has been accurately weighed in advance, and placed in a Soxhlet extractor.

[0256] The extraction was performed for 18 hours using 200 mL of tetrahydrofuran (THF) as a solvent, and the extraction was performed at a reflux rate such that the extraction cycle of the solvent at this time was once every about 5 minutes.

[0257] After the extraction was completed, the cylindrical filter paper was taken out, air-dried, and then vacuum-dried at 40°C for 8 hours, the mass of the cylindrical filter paper including the extraction residue was weighed, and the mass of the extraction residue was calculated by subtracting the mass of the cylindrical filter paper (W2 [g]).

[0258] When recovering THF-soluble substances, the THF-soluble substances can be recovered by fully distilling THF from the THF-soluble substances using an evaporator.

[0259] Next, the amount of components other than the resin component (W3 [g]) is determined by the following procedure (when measuring the THF-insoluble matter of only the resin, W3 is taken as 0 g).

[0260] About 2 g of the toner was accurately weighed (Wa [g]) in a pre-weighed 30 mL porcelain crucible.

[0261] A porcelain crucible was placed in an electric furnace and heated at approximately 900°C for approximately 3 hours, cooled in the furnace, and then cooled in a desiccator at room temperature for more than 1 hour. The mass of the crucible including the incineration residual ash was weighed. The incineration residual ash content (Wb [g]) was calculated by subtracting the mass of the crucible.

[0262] Then, the mass (W3 [g]) of the incineration residual ash in the sample W1 [g] is calculated by the following formula (A).

[0263] W3=W1×(Wb / Wa) (A)

[0264] In this case, the amount of THF-insoluble matter and the amount of incineration-residual ash of the resin component in the toner are determined by the following formulas (B) and (C).

[0265] Ratio of THF-insoluble matter (mass %) = {(W2-W3) / (W1-W3)} × 100 (B)

[0266] Amount of ash remaining after incineration (mass %) = {W3 / (W2-W3)}×100 (C)

[0267] Quantitative method for the amount of carbon-carbon double bonds

[0268] The quantitative method of the amount of carbon-carbon double bonds in the toner and the polyester resin having carbon-carbon double bonds can be exemplified by a method involving measuring protons or carbons of the carbon-carbon double bonds with a nuclear magnetic resonance apparatus (NMR) and performing quantitative determination.

[0269] For the toner, the measurement is performed by recovering the THF-soluble matter in the <Method for measuring the ratio of tetrahydrofuran (THF)-insoluble matter of the resin component>.

[0270] Sample adjustment

[0271] A total of 100 mg of sample, 10 mg of sodium trimethylsilylpropanesulfonate as an internal standard substance, and 10 mg of Cr(AcAc) 3 as a relaxation reagent were weighed into an NMR sample tube, 0.45 ml of a deuterated solvent (eg, heavy pyridine) was added, and the sample was fully dissolved.

[0272] Measurement conditions

[0273] Device: "AVANCE III HD400", manufactured by Bruker BioSpin GmbH

[0274] Number of points: 24,000

[0275] Analysis and calculation

[0276] The amount of double bonds (mmol / g) was calculated from the area ratio of the peaks of carbons derived from double bonds of the unsaturated carboxylic acid component and the unsaturated alcohol component to the peak of carbons derived from the methyl group of the internal standard substance.

[0277] For example, in the case where the carbon-carbon double bonds are derived from an unsaturated carboxylic acid component such as maleic acid or fumaric acid, the amount of double bonds (mmol / g) is calculated from the area ratio of the peak (164.6 ppm) of the double bonds derived from the unsaturated carboxylic acid component and the area ratio of the peak (0 ppm) of the carbon of the methyl portion of the internal standard substance.

[0278] Measurement method of weight average particle size (D4) and number average particle size (D1)

[0279] The weight average particle size (D4) and number average particle size (D1) of the toner were calculated in the following order. A precision particle size distribution measuring device (trade name: Coulter Counter Multisizer 3) based on the pore resistance method and equipped with a 100 μm orifice was used as the measuring device. The dedicated software included with the device (trade name: Beckman Coulter Multisizer 3, version 3.51, manufactured by Beckman Coulter, Inc.) was used to set the measurement conditions and analyze the measurement data. The measurement was performed using 25,000 effective measurement channels.

[0280] As the aqueous electrolyte solution to be used for measurement, a solution prepared by dissolving special grade sodium chloride in ion exchange water to a concentration of about 1% by mass, for example, “ISOTON II” (manufactured by Beckman Coulter, Inc.) can be used.

[0281] Prior to measurement and analysis, the dedicated software was set as follows.

[0282] On the "Change Standard Measurement Method (SOM)" screen of the dedicated software, set the total count in control mode to 50,000 particles, the number of measurements to 1, and the value obtained using "Standard Particles 10.0 μm" (manufactured by Beckman Coulter, Inc.) as the Kd value. Press the "Threshold / Noise Level Measurement Button" to automatically set the threshold and noise level. Also, set the current to 1600 μA, the gain to 2, the electrolyte solution to ISOTON II, and check the "Post-Measurement Orifice Tube Rinse" checkbox.

[0283] In the "Pulse to Particle Size Conversion Settings" screen of the dedicated software, set the element spacing to logarithmic particle size, set the particle size element to 256 particle size elements, and set the particle size range to 2 μm to 60 μm.

[0284] The specific measurement method is described below.

[0285] (1) Place approximately 200 mL of the electrolyte aqueous solution in a 250 mL glass round-bottom beaker dedicated to the Multisizer 3. Place the beaker on the sample stage and stir the sample counterclockwise at 24 revolutions per second using a stirring rod. Remove any dirt and bubbles from the nozzle using the "Flush nozzle" function in the dedicated software.

[0286] (2) About 30 mL of an aqueous electrolyte solution was placed in a 100 mL glass flat-bottom beaker. Then, about 0.3 mL of a dilution solution obtained by diluting a 10% by mass aqueous solution of "CONTAMINON N" (a neutral detergent for cleaning precision measuring instruments having a pH of 7, comprising a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) by 3 times by mass with ion-exchanged water was added thereto as a dispersant.

[0287] (3) An ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) having a power output of 120 W and in which two oscillators having an oscillation frequency of 50 kHz were built in with a phase shift of 180 degrees was prepared. About 3.3 L of ion-exchanged water was placed in a water tank of the ultrasonic disperser, and about 2 mL of CONTAMINON N was added to the water tank.

[0288] (4) The beaker of (2) above is placed in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is started. Then, the height position of the beaker is adjusted to maximize the resonance state of the liquid surface of the aqueous electrolyte solution in the beaker.

[0289] (5) While the electrolyte aqueous solution in the beaker of (4) is being irradiated with ultrasonic waves, approximately 10 mg of the toner is gradually added to the electrolyte aqueous solution and dispersed therein. The ultrasonic dispersion treatment is then continued for another 60 seconds. During the ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to a temperature of 10° C. to 40° C.

[0290] (6) The electrolyte aqueous solution of (5) above, in which the toner is dispersed, is added dropwise to the round-bottom beaker of (1) above, which is set in the sample stage, using a pipette, and the measurement concentration is adjusted to about 5%. Then, measurement is performed until the number of particles measured reaches 50,000.

[0291] (7) Use the dedicated software included with the device to analyze the measurement data and calculate the weight-average particle size (D4) and number-average particle size (D1). When the dedicated software is set to Graph / Volume %, the "Average Diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the weight-average particle size (D4). When the dedicated software is set to Graph / Number %, the "Average Diameter" on the "Analysis / Number Statistics (Arithmetic Mean)" screen is the number-average particle size (D1).

[0292] Method for measuring storage elastic modulus G'

[0293] In the toner of the present invention, the storage elastic modulus G' is measured using a viscoelasticity measuring device (rheometer) ARES (manufactured by Rheometrics Scientific, Inc.) The overview of the measurement is described in ARES Operation Manuals 902-30004 (August 1997 edition) and 902-00153 (July 1993 edition) issued by Rheometrics Scientific Inc. and is as follows.

[0294] Measuring fixture: torsion rectangle

[0295] Measurement sample: For the toner, a rectangular parallelepiped sample having a width of about 12 mm, a height of about 20 mm, and a thickness of about 2.5 mm was produced using a press molding machine (maintaining 15 kN for 1 minute at room temperature). As the press molding machine, a 100 kN press machine NT-100H manufactured by NPa System Co., Ltd. was used.

[0296] The fixture and sample were allowed to stand at room temperature (23°C) for 1 hour, and the sample was mounted on the fixture (see Figure 1 ). As shown in the figure, the sample was fixed so that the width of the measurement portion was about 12 mm, the thickness was about 2.5 mm, and the height was 10.0 mm. After adjusting the temperature to the measurement start temperature of 30° C. for 10 minutes, measurement was performed under the following settings.

[0297] Measurement frequency: 6.28 rad / s

[0298] Measurement distortion setting: The initial value was set to 0.1% and measurement was performed in the automatic measurement mode.

[0299] Sample elongation correction: Adjust in automatic measurement mode.

[0300] Measuring temperature: Raise the temperature from 30°C to 180°C at a rate of 2°C per minute.

[0301] Measurement interval: Viscoelasticity data were measured every 30 seconds (ie, every 1°C).

[0302] The data were transferred via an interface to RSI Orchestrator (control, data acquisition and analysis software) (manufactured by Rheometrics Scientific, Inc.) running on Microsoft Windows 7.

[0303] The values ​​of storage modulus G'(50), G'(100), and G'(T150) at each temperature of 50°C, 100°C, and 150°C were read.

[0304] Method for measuring glass transition temperature Tg

[0305] The glass transition temperature Tg of the THF-insoluble matter of the resin component in the toner was measured using a differential scanning calorimeter "Q2000" (manufactured by TA Instruments) in accordance with ASTM D3418-82. The melting points of indium and zinc were used to correct the temperature of the device detection unit, and the heat of fusion of indium was used to correct the heat of heat.

[0306] Regarding the THF-insoluble matter of the resin component, the extraction residue of the toner in the <Method for Measuring the Ratio of Tetrahydrofuran (THF)-Insoluble Matter of the Resin Component> is recovered from the cylindrical filter paper.

[0307] Specifically, about 2 mg of the extraction residue was accurately weighed and placed in an aluminum pan, an empty aluminum pan was used as a reference, and measurement was performed in a measurement temperature range from -10°C to 200°C at a temperature increase rate of 10°C / min.

[0308] In the measurement, the temperature was once raised to 200°C, then lowered to -10°C, and then raised again. During the second temperature increase, the specific heat change was measured within the temperature range of 30°C to 100°C. The intersection of this differential thermal curve and the line at the midpoint of the baseline before and after the specific heat change was defined as the glass transition temperature Tg.

[0309] Measurement of Weight Average Molecular Weight Mw, Number Average Molecular Weight Mn, and Peak Top Molecular Weight Mp (Measurement of Molecular Weight Distribution of Release Agent, Resin, and Toner's THF-Soluble Matter)

[0310] The molecular weight distribution of THF-soluble matter of the releasing agent and the toner and resin such as polymer A is measured by gel permeation chromatography (GPC) in the following manner.

[0311] First, the sample was dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The obtained solution was then filtered through a solvent-resistant membrane filter "MAISHORI DISK" (manufactured by Tosoh Corporation) having a pore size of 0.2 μm to obtain a sample solution. The sample solution was adjusted to a concentration of 0.8% by mass of THF-soluble matter. The sample solution was used for measurement under the following conditions.

[0312] Apparatus: HLC8120 GPC (detector: RI) (manufactured by Tosoh Corporation)

[0313] ·Column: Septal column, Shodex KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko KK)

[0314] Eluent: Tetrahydrofuran (THF)

[0315] Flow rate: 1.0 ml / min

[0316] Oven temperature: 40.0℃

[0317] Sample injection volume: 0.10ml

[0318] When calculating the molecular weight of the sample, a molecular weight calibration curve created using a standard polystyrene resin (e.g., trade name "TSK standard polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corp.) is used.

[0319] Methods used to measure melting point

[0320] The melting points of the polymer A, the polyester resin, the releasing agent, and the like were measured using DSC Q1000 (manufactured by TA Instruments) under the following conditions.

[0321] Heating rate: 10℃ / min

[0322] Measurement start temperature: 20°C

[0323] Measurement end temperature: 180℃

[0324] The melting points of indium and zinc are used for temperature correction of the detection unit of the device, and the heat of fusion of indium is used for caloric correction.

[0325] Specifically, about 5 mg of a sample was accurately weighed and placed in an aluminum pan, and differential scanning calorimetry was performed, using an empty aluminum pan as a reference.

[0326] The peak temperature of the maximum endothermic peak in the first heating process was taken as the melting point.

[0327] The maximum endothermic peak is a peak having the largest endothermic amount when a plurality of peaks exist.

[0328] Measurement of the heat absorption of tetrahydrofuran-insoluble matter in resin components of toner

[0329] The heat absorption of the tetrahydrofuran-insoluble matter in the toner is measured using DSC Q1000 (manufactured by TA Instruments) under the following conditions.

[0330] Heating rate: 10℃ / min

[0331] Measurement start temperature: 20°C

[0332] Measurement end temperature: 180℃

[0333] The melting points of indium and zinc are used for temperature correction of the detection unit of the device, and the heat of fusion of indium is used for caloric correction.

[0334] Specifically, about 5 mg of the extraction residue described in the method for measuring the amount of THF-insoluble matter was accurately weighed and placed in an aluminum pan, and differential scanning calorimetry was performed using an empty aluminum pan as a reference.

[0335] During the measurement, the temperature was once raised to 200°C, then lowered to 10°C, and then raised again. In the DSC curve obtained during this temperature increase process, the temperature Tm at the peak top of the maximum endothermic peak in the temperature range from 10°C to 200°C was determined. The endothermic heat H of the endothermic peak of the extraction residue is the integrated value of the endothermic peak. The endothermic heat (H(I)) of the present invention is calculated by the following formula (E).

[0336] Heat absorption (H(I)) (J / g) = {H×W2 / (W2-W3)}×100 (E)

[0337] Measurement of toner aggregation

[0338] In the toner, a powder tester (manufactured by Hosokawa Micron Co., Ltd.) was used as a device for measuring the degree of aggregation. As a measurement method, a 400-mesh (opening 38 μm) sieve, a 200-mesh (opening 75 μm) sieve, and a 100-mesh (opening 150 μm) sieve were placed on a vibration table in the order of narrow openings, that is, the 400-mesh, 200-mesh, and 100-mesh sieves were stacked in this order and arranged so that the 100-mesh sieve was on top.

[0339] A total of 5 g of accurately weighed sample was added to a 100-mesh sieve, the input voltage to the vibration table was controlled to adjust the amplitude of the vibration table to within the range of 60 μm to 90 μm, and vibration was applied (rheostat scale of about 2.5) for about 15 seconds. The mass of the sample remaining on each sieve was then measured to obtain the degree of aggregation according to the following formula.

[0340] (Aggregation degree) = (mass of toner carried on 100 mesh) / (mass of toner initially carried on the sieve) + (mass of toner carried on 200 mesh) / (mass of toner initially carried on the sieve) × 3 / 5 + (mass of toner carried on 400 mesh) / (mass of toner initially carried on the sieve) × 1 / 5

[0341] Measurement of resin softening point (1 / 2 outflow temperature)

[0342] The softening point (1 / 2 outflow temperature) of the resin can be measured using a constant load extrusion type capillary rheometer "Flow Characteristics Evaluation Device Flow Tester CFT-500D" (manufactured by Shimadzu Corporation).

[0343] The CFT-500D is a device that melts a measurement sample filled in a cylinder by increasing the temperature while applying a constant load from the top with a piston and extrude the measurement sample from a narrow tube hole at the bottom of the cylinder. A flow curve can be drawn from the piston's descending amount (mm) and temperature (°C) at this time.

[0344] In the present invention, the "melting temperature in the 1 / 2 method" described in the manual attached to the "Flow Characteristics Evaluation Device Flow Tester CFT-500D" is taken as the softening point (1 / 2 outflow temperature).

[0345] The melting temperature in the 1 / 2 method is calculated as follows.

[0346] First, 1 / 2 of the difference between the piston descent amount at the end of outflow (outflow end point, Smax) and the piston descent amount at the start of outflow (lowest point, Smin) is obtained (this is represented by X. X = (Smax - Smin) / 2). Then, the temperature of the flow curve when the piston descent amount becomes the sum of X and Smin is taken as the melting temperature in the 1 / 2 method.

[0347] Method for measuring acid value

[0348] The acid value is the mass [mg] of potassium hydroxide required to neutralize the acids contained in 1g of the sample. That is, the mass [mg] of potassium hydroxide required to neutralize the free fatty acids and resin acids contained in 1g of the sample is called the acid value.

[0349] The acid value is measured according to JIS K 0070-1992. Specifically, it is measured according to the following procedure.

[0350] (1) Preparation of reagents

[0351] A total of 1.0 g of phenolphthalein was dissolved in 90 mL of ethanol (95 volume %), and ion-exchanged water was added to make 100 mL and obtain a phenolphthalein solution.

[0352] A total of 7 g of special grade potassium hydroxide was dissolved in 5 mL of water and ethanol (95% by volume) was added to make 1 L. The solution was placed in an alkali-resistant container and allowed to stand for 3 days to prevent contact with carbon dioxide, etc. After standing, the solution was filtered to obtain a potassium hydroxide solution. The potassium hydroxide solution obtained was stored in an alkali-resistant container.

[0353] A total of 25 mL of 0.1 mol / L hydrochloric acid was placed in an Erlenmeyer flask, a few drops of phenolphthalein solution were added, titrated with the above potassium hydroxide solution, and the factor of the potassium hydroxide solution was determined from the amount of potassium hydroxide solution required for neutralization. 0.1 mol / L hydrochloric acid prepared according to JIS K 8001-1998 was used.

[0354] (2) Operation

[0355] (A) Main test

[0356] A total of 2.0 g sample is placed in a 200 mL Erlenmeyer flask and accurately weighed, a mixed solution of 100 mL toluene / ethanol (2: 1) is added, and the sample is dissolved over 5 hours. The solution is then added with a few drops of phenolphthalein solution as an indicator, and titrated using potassium hydroxide solution. The endpoint of the titration is when the light red color of the indicator continues for 30 seconds.

[0357] (B) Blank test

[0358] The same titration as above was performed except that no sample was added (ie, only a mixed solution of toluene / ethanol (2:1) was used).

[0359] (3) Calculation of acid value

[0360] The obtained result was substituted into the following formula to calculate the acid value.

[0361] AV=[(BA)×f×5.61] / S

[0362] In the above formula, AV represents the acid value [mg KOH / g], A represents the amount of potassium hydroxide solution added in the blank test [mL], B represents the amount of potassium hydroxide solution added in the main test [mL], f represents the factor of the potassium hydroxide solution, and S represents the mass of the sample [g].

[0363] Example

[0364] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited thereto. Parts used in Examples are based on mass unless otherwise specified.

[0365] Production Example of Polymer A1

[0366] The following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere.

[0367]

[0368] 3.0 parts of tert-butyl peroxypivalate (manufactured by Nippon Oil & Fat Corp.: PERBUTYL PV)

[0369] While stirring the interior of the reaction vessel at 200 rpm, the material was heated to 70°C and subjected to polymerization for 12 hours to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. Subsequently, the temperature of the solution was lowered to 25°C, and then the solution was poured into 1000.0 parts of methanol while stirring to precipitate methanol-insoluble matter. The obtained methanol-insoluble matter was separated by filtration, further washed with methanol, and vacuum-dried at 40°C for 24 hours to obtain Polymer A1.

[0370] The polymer A1 had a weight average molecular weight of 14,000, an acid value of 0.0 mg KOH / g, and a melting point Tm of 61.0°C.

[0371] Production Examples of Polymers A2 to A7

[0372] Polymers A2 to A7 were synthesized under the same conditions except that the addition amounts of the polymerizable monomers A, B, and C were changed as shown in Table 1. Table 1 shows various physical properties of polymers A2 to A7.

[0373] [Table 1]

[0374]

[0375] Production Example of Polyester Resin B1

[0376] The following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere.

[0377]

[0378] The above materials were reacted at 230°C for 2 hours under a nitrogen stream while distilling off the generated water. Next, the reaction was carried out under a reduced pressure of 2.5 kPa for 5 hours, and then the temperature was lowered to 180°C. A total of 1 part of tert-butylcatechol was added as a polymerization inhibitor, and 60.0 parts of fumaric acid was further added. The components were reacted under a reduced pressure of 0.5 to 2.5 kPa for 8 hours, and the reaction product was collected as polyester resin B1.

[0379] The amount of double bonds in the polyester resin B1 was 0.39 mmol / g.

[0380] Production Examples of Polyester Resins B2 to B12

[0381] Polyester resins B2 to B12 were synthesized under the same conditions except that the addition amount of each monomer in the production example of polyester resin B1 was changed as shown in Table 2. Table 2 shows various physical properties.

[0382] [Table 2]

[0383]

[0384] BPA-2EO: Bisphenol A-ethylene oxide 2mol adduct

[0385] BPA-2PO: Bisphenol A-propylene oxide 2 mol adduct

[0386] Production Example of Polyester Resin B13

[0387] The following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere.

[0388]

[0389] The above materials were reacted at 230° C. for 2 hours under a nitrogen stream while distilling off the generated water. Next, the reaction was carried out under a reduced pressure of 2.5 kPa for 5 hours, and then the temperature was lowered to 180° C. The reaction was further carried out under a reduced pressure of 0.5 kPa to 2.5 kPa for 8 hours, and the reaction product was collected as polyester resin B13.

[0390] The amount of double bonds in the polyester resin B13 was 3.0 mmol / g, the melting point Tm was 112° C., and the weight average molecular weight Mw was 25,000.

[0391] Production Example of Polyester Resin B14

[0392] The following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere.

[0393]

[0394] The above materials were reacted at 230° C. for 2 hours under a nitrogen stream while distilling off the generated water. Next, the reaction was carried out under a reduced pressure of 2.5 kPa for 5 hours, and then the temperature was lowered to 180° C. After further reacting under a reduced pressure of 0.5 to 2.5 kPa for 8 hours, the reaction product was taken out to obtain polyester resin B14.

[0395] The polyester resin B14 had a Tg of 61° C. and an acid value of 24.3 mg KOH / g.

[0396] Production Example of Binder Resin C1

[0397] A total of 60 parts of polymer A1 and 40 parts of polyester resin B1 were mixed and fed to a twin-screw kneader (manufactured by Kurimoto Iron Works, Ltd., S5KRC kneader) at 40 kg / h. Simultaneously, 4.0 parts of tert-butyl peroxyisopropyl monocarbonate (t-butyl peroxyisopropyl monocarbonate) was fed at 0.4 kg / h as a radical reaction initiator. The mixture was kneaded and extruded at 160°C for 5 minutes at 100 rpm to allow the reaction to proceed. The mixture was then mixed while nitrogen was allowed to flow from the exhaust port to remove the organic solvent. The resulting mixture was cooled to obtain binder resin C1.

[0398] The obtained binder resin C1 has a polymer A1 site as a crystalline site and a non-crystalline modified resin site in which the polymer A1 and the polyester resin B1 are cross-linked via a carbon-carbon bond as a non-crystalline site.

[0399] Production Examples of Binder Resins C2 to C32

[0400] Binder resins C2 to C32 were synthesized under the same conditions except that the types and addition amounts of polymer A1 and polyester resin B1 and the addition amount of the radical reaction initiator were changed in the production example of binder resin C1 as shown in Table 3. Table 3 shows various physical properties.

[0401] The obtained binder resins C2 to C28 have a site corresponding to the kind of polymer A used as a crystalline site and an amorphous modified resin site as an amorphous site in which resins respectively corresponding to the used polymer A and polyester resin B are cross-linked through carbon-carbon bonds.

[0402] In the obtained binder resins C29 to C31, crosslinking between molecules of the polyester resin was confirmed, but crosslinking between the polymer A and the polyester resin was not confirmed.

[0403] Furthermore, it was not confirmed that the obtained binder resin C32 had a cross-linked structure.

[0404] [Table 3]

[0405]

[0406] Production Example of Toner Particles 1

[0407] Binder resin C1 100.0 parts

[0408] Spherical magnetic iron oxide particles (number average particle size of primary particles: 0.20 μm, Hc = 6.0 kA / m, σs = 85.2 Am 2 / kg, σr=6.5Am 2 / kg) 95.0 parts

[0409] Release agent 1 (EXCEREX 15341PA, molecular weight (Mp) 1700, melting point 89° C., manufactured by Mitsui Chemicals, Inc.) 4.0 parts

[0410] Charge control agent T-77 (manufactured by Hodogaya Chemical Co., Ltd.) 2.0 parts

[0411] The above materials were preliminarily mixed with an FM mixer (manufactured by Nippon Coke Industry Co., Ltd.), and then melt-kneaded at a set temperature of 160°C by a twin-screw kneading extruder (PCM-30 model manufactured by Ikegai Tekko Co., Ltd.).

[0412] The obtained kneaded product was cooled, coarsely pulverized with a hammer mill, and then pulverized with a mechanical pulverizer (T-250 manufactured by Turbo Kogyo Co., Ltd.) The obtained finely pulverized powder was classified using a multi-classifier utilizing the Coanda effect to obtain toner particles 1 having a weight average particle size (D4) of 7.1 μm.

[0413] Production Example of Toner 1

[0414] A total of 100 parts of toner particles 1 and 2.0 parts of hydrophobic silica fine powder (number average particle size of primary particles: 10 nm, BET specific surface area of ​​primary silica: 200 m 2 / g) was externally added and mixed to obtain Toner 1. Table 5 shows the physical properties of Toner 1.

[0415] Production Examples of Toners 2 to 38

[0416] Toner particles 2 to 38 were obtained by changing the binder resin C1 and the release agent (described in Table 4) used in the production example of toner particle 1 as shown in Table 4. Furthermore, toner particles 2 to 38 were obtained in the same manner as in the production example of toner 1, except that the toner particles used were changed. Table 5 shows the physical properties.

[0417] [Table 4]

[0418]

[0419] [Table 5]

[0420]

[0421]

[0422] The unit of particle size is μm.

[0423] [Table 6]

[0424]

[0425] The unit of Tm is °C.

[0426] EXCEREX 15341PA, EXCEREX 30050B, EXCEREX 20700, Hi-Wax HP10A, Hi-Wax2203A were purchased from Mitsui Chemicals, Inc.

[0427] C105 was purchased from Sasol.

[0428] HNP9 was purchased from Nipon Seiro Co., Ltd.

[0429] Production Example of Binder Resin C33

[0430] A total of 50.0 parts of polyester resin B13 and 50.0 parts of polyester resin B14 were mixed and the mixture was fed to a twin-screw kneader (manufactured by Kurimoto Iron Works, Ltd., S5KRC kneader) at 40 kg / h. At the same time, 4.0 parts of tert-butyl peroxyisopropyl monocarbonate as a free radical reaction initiator were fed at 0.4 kg / h and reacted by kneading and extruding at 100 rpm at 160°C for 5 minutes. The mixture was then mixed while nitrogen was allowed to flow from the exhaust port to remove the organic solvent. The obtained mixture was cooled to obtain binder resin C33. The number average molecular weight Mn was 14,200 and the weight average molecular weight Mw was 53,300.

[0431] Production Example of Toner Particles 39

[0432] Binder resin C33 100.0 parts

[0433] Spherical magnetic iron oxide particles (number average particle size of primary particles: 0.20 μm, Hc = 6.0 kA / m, σs = 85.2 Am 2 / kg, σr=6.5Am 2 / kg) 95.0 parts

[0434] Release agent 1 (EXCEREX 15341PA, molecular weight (Mp) 1700, melting point 89° C., manufactured by Mitsui Chemicals, Inc.) 4.0 parts

[0435] Charge control agent T-77 (manufactured by Hodogaya Chemical Co., Ltd.) 2.0 parts

[0436] The above materials were preliminarily mixed with an FM mixer (manufactured by Nippon Coke Industry Co., Ltd.), and then melt-kneaded at a set temperature of 160°C by a twin-screw kneading extruder (PCM-30 model manufactured by Ikegai Tekko Co., Ltd.).

[0437] The obtained kneaded product was cooled, coarsely pulverized with a hammer mill, and then pulverized with a mechanical pulverizer (T-250 manufactured by Turbo Kogyo Co., Ltd.) The obtained finely pulverized powder was classified using a multi-classifier utilizing the Coanda effect to obtain toner particles 39 having a weight average particle size (D4) of 7.0 μm.

[0438] Production Example of Toner 39

[0439] A total of 100 parts of toner particles 39 and 2.0 parts of hydrophobic silica fine powder (number average particle size of primary particles: 10 nm, BET specific surface area of ​​primary silica: 200 m 2 / g) was externally added and mixed to obtain Toner 39. Table 5 shows the physical properties of Toner 39.

[0440] Evaluation Method

[0441] Example 1

[0442] The evaluation machine was a commercially available magnetic one-component printer HP LaserJet Enterprise M609dn (manufactured by Hewlett-Packard Co.: process speed 420 mm / s). The following evaluation using Toner 1 was performed with the evaluation machine.

[0443] Evaluation of low-temperature fixability

[0444] The low-temperature fixability was evaluated using an external fixing device obtained by taking out the fixing device of M609dn and modifying it so that the fixing device temperature could be arbitrarily set and the process speed was set to 450 mm / sec.

[0445] As the evaluation paper, A4 paper ("PROBER coated paper": 105 g / m 2 , manufactured by Fox River Paper Co.). The development contrast of M609dn was adjusted so that the toner lay-up on the paper was 0.6 / cm 2, and a "solid" unfixed image with a top margin of 5 mm, a width of 100 mm, and a length of 100 mm was created in a normal temperature and humidity environment (temperature 23.0° C. / relative humidity 50%) in monochrome mode.

[0446] In addition, the pressure during fixing was set to 1.00 kgf / cm 2 . Using a modified fixing device, the fixing temperature was raised by 5°C at a time within a range from 80°C to 140°C under a normal temperature and humidity environment (temperature 23°C / relative humidity 50%) and kept constant for 3 minutes to obtain a fixed image of each unfixed image at each temperature. The temperature at which no white spots appeared on the obtained fixed image was defined as the fixing start temperature, and the low-temperature fixing property was evaluated according to the following evaluation criteria. In the present invention, grades A to C were judged to correspond to satisfactory low-temperature fixing property. Table 7 shows the evaluation results.

[0447] Evaluation Criteria

[0448] A: The fixing start temperature is lower than 120℃

[0449] B: Fixing start temperature is 120°C or higher and lower than 130°C

[0450] C: Fixing start temperature is 130°C or higher and lower than 140°C

[0451] D: Fixing start temperature is 140℃ or above

[0452] Evaluation of concentration unevenness

[0453] A total of 100 solid images were continuously output as sample images using the M609dn at a normal temperature and humidity environment (23°C, 60% RH), and the last five images were obtained. Nine points were uniformly selected for each solid image obtained, and the reflection density was measured using an SPI filter with a Macbeth densitometer (manufactured by Macbeth Co.) as a reflection densitometer.

[0454] The difference between the maximum and minimum density values ​​at nine points was calculated, and the average of these differences for five images was used to evaluate image unevenness during fixing. In the present invention, grades A to C were determined to correspond to satisfactory density unevenness. Table 7 shows the evaluation results.

[0455] Evaluation Criteria

[0456] A: less than 0.04

[0457] B: 0.04 or more and less than 0.06

[0458] C: 0.06 or more and less than 0.08

[0459] D: 0.08 or more

[0460] Evaluation of heat fouling resistance

[0461] The hot offset resistance was evaluated using an external fixing device obtained by taking out the fixing device of M609dn and modifying it so that the fixing device temperature can be set arbitrarily and the process speed is set to 450 mm / sec. As the evaluation paper, A4 paper ("PROBER coated paper": 105 g / m 2 , manufactured by Fox River Paper Co.).

[0462] Adjust the development contrast of M609dn so that the toner loading on the paper is 0.3 / cm 2 , and a "solid" unfixed image with a top margin of 5 mm, a width of 100 mm, and a length of 100 mm was created in a normal temperature and humidity environment (temperature 23.0° C. / relative humidity 50%) in monochrome mode.

[0463] In addition, the pressure during fixing was set to 1.00 kgf / cm 2 Using a modified fixing device, a fixed image at 180°C was obtained in a normal temperature and humidity environment (temperature 23°C / relative humidity 50%). The density was measured when defacement occurred during the second round of fixing of the fixing roller on the rear end side of the "solid" portion. The reflection density was measured using an SPI filter with a Macbeth densitometer (manufactured by Macbeth Co.) as a reflection densitometer, and the difference between this and the white background portion was taken as the defacement density.

[0464] Hot offset resistance was evaluated according to the following evaluation criteria: In the present invention, grades A to C were judged to correspond to satisfactory hot offset resistance. Table 7 shows the evaluation results.

[0465] Evaluation Criteria

[0466] A: No stain is seen, or the stain concentration on the second circle is less than 0.02

[0467] B: The contamination concentration on the second circle is 0.02 or more and less than 0.05

[0468] C: The contamination concentration on the second circle is 0.05 or more and less than 0.10

[0469] D: The contamination concentration on the second circle is 0.10 or more

[0470] Evaluation of heat-resistant storage stability

[0471] Toner 1 was accurately weighed twice, totaling 5g, and allowed to stand for 24 hours in an environment at 23°C and 60% RH, and again at 30°C and 80% RH. The degree of aggregation of the toner after each stand was measured using the "Measurement of Toner Aggregation Degree" method described above. The rate of increase in the degree of aggregation of the toner after standing at 30°C and 80% RH, with the degree of aggregation of the toner after standing at 23°C and 60% RH being 100%, was evaluated according to the following criteria. The smaller the rate of increase, the better the heat-resistant storage stability. Table 7 shows the evaluation results.

[0472] Evaluation Criteria

[0473] A: The increase in aggregation is less than 5%

[0474] B: The increase rate of aggregation is 5% or more and less than 10%

[0475] C: The increase rate of aggregation is 10% or more and less than 20%

[0476] D: The increase in aggregation rate is more than 20%

[0477] Evaluation of the reduction rate of triboelectric charge of toner due to continuous vibration

[0478] First, 1.0 g of toner and 19.0 g of magnetic carrier (Japan Imaging Society standard carrier, spherical carrier with a surface-treated ferrite core (N-01)) were placed in a plastic bottle and allowed to stand in a normal temperature and humidity environment (temperature 23°C, relative humidity 50%) for 24 hours.

[0479] The above magnetic carrier and toner are placed in a plastic bottle with a cap and shaken at a reciprocating speed of 4 times per second for 1 minute using a shaker (YS-LD, manufactured by Yayoi Co., Ltd.) to prepare a two-component developer composed of toner and carrier in which the toner is charged.

[0480] Next, use Figure 2 The measuring device shown in measures the triboelectric charge. Figure 2 In the embodiment, about 0.5 g of the above two-component developer is placed in a metal measuring container 2 having a 500-mesh sieve 3 at the bottom, and a metal cover 4 is placed thereon. At this time, the total mass of the measuring container is weighed and taken as W1 (kg).

[0481] Next, in the suction device 1 (at least the portion in contact with the measuring container 2 is insulated), suction is applied from the suction port 7, and the air volume control valve 6 is adjusted so that the pressure of the vacuum gauge 5 reaches 2.5 kPa. In this state, suction is continued for two minutes to remove the toner from the developer. The potential of the potentiometer 9 at this time is represented by V (volts). Reference numeral 8 represents a capacitor, and the capacitance is C (mF). The mass of the entire measuring container after suction is weighed and represented by W2 (g).

[0482] The triboelectric charge Q(1) [mC / kg] of the sample when vibrated for 1 minute was calculated by the following formula (5).

[0483] Q(1)[mC / kg]=(C×V) / (W1-W2) (5)

[0484] The triboelectric charge Q(30) was measured in a similar manner when the vibration was performed at a speed of 4 reciprocating times per second for 30 minutes. The triboelectric charge reduction rate in the present invention was calculated by the following formula.

[0485] (Frictional charge reduction rate) (%) = {(Q(1) - Q(30)) / Q(1)} × 100

[0486] In this evaluation, the rate of decrease in triboelectric charge refers to the degree of toner degradation caused by friction with the magnetic carrier. A lower rate of decrease is considered to indicate higher stress resistance. In other words, in the present invention, grades A to C are considered to correspond to satisfactory charging performance. Table 7 shows the evaluation results.

[0487] Evaluation Criteria

[0488] A: The decrease rate of friction charge is less than 10%

[0489] B: The reduction rate of friction charge is 10% or more and less than 15%

[0490] C: The reduction rate of friction charge is 15% or more and less than 20%

[0491] D: The reduction rate of friction charge is more than 20%

[0492] Examples 2 to 32

[0493] Evaluation was performed in the same manner as in Example 1 except that Toners 2 to 32 were used. Table 7 shows the evaluation results.

[0494] Comparative Examples 1 to 7

[0495] Evaluation was performed in the same manner as in Example 1, except that Toners 33 to 39 were used.

[0496] [Table 7]

[0497]

[0498] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments. The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. A toner, characterized in that: It contains A resin containing a non-crystalline part and a crystalline part as a binder resin, wherein The ratio of tetrahydrofuran-insoluble matter in the resin component is 40% by mass to 80% by mass, The ratio is calculated by the following formula: The ratio of the tetrahydrofuran-insoluble matter of the resin component=(the mass of the tetrahydrofuran-insoluble matter of the resin component in the toner) / (the mass of the resin component in the toner)×100, In the differential scanning calorimeter measurement of the tetrahydrofuran-insoluble matter, Where the temperature of the maximum endothermic peak is represented by Tm in °C and the amount of endothermic heat is represented by H(I) in J / g, Satisfies the following equations (1) and (2): 55.0≤Tm≤80.0 (1) 10.0≤H(I)≤80.0 (2), The crystalline part is a crystalline vinyl resin part, The crystalline vinyl resin part is a polymer A1 part, and the polymer A1 part is a polymer containing a monomer of a polymerizable monomer A1. The polymerizable monomer A1 is a (meth)acrylate having a chain hydrocarbon group having 18 to 36 carbon atoms, The mass ratio of the polymerizable monomer A1 unit in the polymer A1 portion is 30% by mass to 99% by mass. The non-crystalline site is a non-crystalline modified resin site in which a vinyl resin having crystallinity and a polyester resin are cross-linked with each other through a carbon-carbon bond, and The toner includes a releasing agent having a peak molecular weight of 1000 or more.

2. The toner according to claim 1, wherein the endothermic amount H(I) satisfies the following formula (3): 16.5≤H(I)≤65.0 (3).

3. The toner according to claim 1 or 2, wherein The part of the modified resin part that is derived from the crystalline vinyl resin is a polymer A2 part, and the polymer A2 part is a polymer of monomers including a polymerizable monomer A2. The polymerizable monomer A2 is a (meth)acrylate having a chain hydrocarbon group having 18 to 36 carbon atoms, and The mass ratio of the polymerizable monomer A2 unit in the A2 portion of the polymer is 30% by mass to 99% by mass.

4. The toner according to claim 1 or 2, wherein The binder resin includes: a cross-linked polyester resin site which is the non-crystalline site and in which a vinyl resin having crystallinity and a polyester resin are cross-linked with each other through a carbon-carbon bond; and The vinyl resin part is the crystalline part and has crystallinity. 5 . The toner according to claim 1 , wherein the glass transition temperature of the tetrahydrofuran-insoluble matter of the resin component is from 25° C. to 55° C. 6 . The toner according to claim 1 , wherein an amount of carbon-carbon double bonds in the toner is 0.50 mmol / g or less based on the mass of the toner. 7 . The toner according to claim 1 , wherein the toner has a 1 / 2 outflow temperature in a temperature increase measurement by a constant load extrusion type rheometer of 80° C. to 130° C. 8 . The toner according to claim 1 , wherein the releasing agent has a melting point of 80° C. to 120° C. 9 . The toner according to claim 1 , wherein the releasing agent has an acid value of 5.0 to 20.0 mgKOH / g.

10. The toner according to claim 1 or 2, wherein the acid value of the release agent is AV W The acid value of the non-crystalline part is represented by AV A When expressed, the following formula (4) is satisfied: AV W > AV A (4).

11. The toner according to claim 1 or 2, wherein in the viscoelasticity measurement of tetrahydrofuran-soluble matter of the toner, the storage elastic modulus G'(150) at 150°C is 1.0×10 4 Pa to 1.0×10 7 Pa.

Citation Information

Patent Citations

  • Image forming method and method for manufacturing toner for electrostatic charge image development

    JP2007114635A

  • Method for manufacturing electrophotographic toner

    JP2010145929A

  • Toner binder and toner

    JP2018156074A

  • Toner

    CN103109238A

  • Toner and method for manufacturing toner particles

    CN103988130A